Tackified and filled silicone adhesive composition

Adhesive compositions with polydiorganosiloxane polyoxamide copolymers, silicate tackifying resins, and inorganic fillers address the challenges of damage-free removal and high shear strength in adverse conditions, enhancing adhesion and repositionability.

JP7618539B2Active Publication Date: 2025-01-213M INNOVATIVE PROPERTIES CO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021509980
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-08-23
Filing Date
2019-08-21
Publication Date
2025-01-21
Estimated Expiration
2039-08-21

AI Technical Summary

Technical Problem

Existing adhesive compositions struggle with damage-free removal from substrates, particularly in wet or humid environments, and lack sufficient shear strength and repositionability.

Method used

Adhesive compositions comprising polydiorganosiloxane polyoxamide copolymers, silicate tackifying resins, and inorganic fillers, such as fumed silica, which provide a balance of adhesion, repositionability, and high shear strength, even in adverse conditions.

Benefits of technology

The compositions enable damage-free removal, repositionability, and high shear strength, reducing adhesive residue and substrate damage, even in wet or humid conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618539000001
    Figure 0007618539000001
  • Figure 0007618539000002
    Figure 0007618539000002
  • Figure 0007618539000003
    Figure 0007618539000003
Patent Text Reader

Abstract

The present disclosure generally relates to adhesive compositions and articles comprising at least one of a polydiorganosiloxane polyoxamide copolymer, a silicone polyurea block copolymer, and / or an addition-cured silicone, a silicate tackifying resin, and an inorganic particle filler. The filler is typically fumed silica. Some embodiments of the adhesive composition include a polydiorganosiloxane polyoxamide copolymer, about 10% to about 70% by weight of the silicate tackifying resin, and about 0.1% to about 20% by weight of the inorganic particle filler; a silicone polyurea block copolymer, about 10% to about 70% by weight of the silicate tackifying resin, and about 0.1% to about 20% by weight of the inorganic particle filler; and an addition-cured silicone, about 10% to about 70% by weight of the silicate tackifying resin, and about 0.1% to about 20% by weight of the inorganic particle filler.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates generally to adhesive compositions and articles comprising a silicone polymer, a silicate tackifying resin, and an inorganic filler. Summary of the Invention

[0002] The inventors of the present disclosure have discovered that an adhesive composition or article comprising at least one of: (1) a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% to about 20% by weight; (2) a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% to about 20% by weight; and (3) an addition cure silicone, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% to about 20% by weight, has various advantages or benefits. Adhesive articles featuring such adhesive compositions exhibit at least one of damage-free removal, repositionability, and high shear strength, even in wet or humid environments. Currently preferred adhesive compositions exhibit all three. Such compositions can also exhibit reduced adhesion to certain silicone release liners, allowing the user to quickly prepare an article for object attachment or other adhesive-related tasks.

[0003] Adhesive compositions, adhesive articles, and methods of making adhesive articles are provided. The polydiorganosiloxane polyoxamide copolymers can contain a relatively large fraction of polydiorganosiloxanes compared to many known polydiorganosiloxane polyamide copolymers. The adhesive compositions can be formulated as either pressure sensitive or heat activated adhesives.

[0004] In a first aspect, an adhesive composition is provided that includes at least one of: (1) a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of about 10% by weight to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% by weight to about 20% by weight; (2) a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 10% by weight to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% by weight to about 20% by weight; and (3) an addition cure silicone, a silicate tackifying resin in an amount of about 10% by weight to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% by weight to about 20% by weight. The inorganic filler is typically fumed silica. In some embodiments, the polydiorganosiloxane polyoxamide contains at least two repeating units of formula I. [ka]

[0005] In this formula, each R 1 is independently alkyl, haloalkyl, aralkyl, alkenyl, aryl, or aryl substituted with alkyl, alkoxy, or halo; R 1 At least 50 percent of the groups are methyl. Each Y is independently an alkylene, an aralkylene, or a combination thereof. The subscript n is independently an integer from 40 to 1500, and the subscript p is an integer from 1 to 10. The group G is a group of formula R 3 HN-G-NHR 3 From diamine, two -NHR 3 The group R is a divalent group that is a residue unit equal to the unit R minus the group (i.e., the amino group). 3 is hydrogen or alkyl, or R 3together with G and the nitrogen to which they are both attached form a heterocyclic group. Each asterisk (*) indicates the site at which the repeat unit attaches to another group within the copolymer, such as another repeat unit of Formula I. In some embodiments, the silicone-containing polymer is formed by an addition cure reaction between vinyl-terminated poly(dimethylsiloxane) (PDMS) and hydrogen-terminated PDMS in the presence of a hydrosilylation catalyst (e.g., a platinum complex).

[0006] In a second aspect, an article is provided that includes a substrate and an adhesive layer adjacent at least one surface of the substrate, the adhesive layer including at least one of: (1) a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of about 0.1% to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% to about 20% by weight, (2) a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% to about 20% by weight, and (3) an addition cure silicone, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% to about 20% by weight.

[0007] In a third aspect, a method of making an article is provided. The method includes providing a substrate and applying an adhesive composition to at least one surface of the substrate. The adhesive composition includes at least one of: (1) a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of about 0.1% to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% to about 20% by weight; (2) a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% to about 20% by weight; and (3) an addition cure silicone, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and an inorganic particulate filler in an amount of about 0.1% to about 20% by weight.

[0008] The above summary of the present disclosure is not intended to describe each disclosed embodiment or every implementation of the present disclosure. The following description more particularly illustrates exemplary embodiments. In several places throughout the specification, explanations are provided through lists of examples, which examples can be used in various combinations. In each instance, the recited items serve only as a representative group and should not be interpreted as an exclusive list. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Adhesive compositions and articles are provided that include at least one of: (1) a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and an inorganic particle filler in an amount of about 0.1% to about 10% by weight; (2) a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and an inorganic particle filler in an amount of about 0.1% to about 20% by weight; and (3) an addition cure silicone, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and an inorganic particle filler in an amount of about 0.1% to about 20% by weight. The inorganic particle filler is typically fumed silica. The adhesive composition can be either a pressure sensitive or a heat activated adhesive.

[0010] definition The terms "a," "an," and "the" are used interchangeably herein to mean "at least one" and refer to one or more of the elements being described.

[0011] The term "addition cure silicone" refers to a polymer that results in the reaction, typically in the presence of a platinum catalyst, of a vinyl terminated oligomer / polymer, such as a vinyl terminated polydimethylsiloxane (PDMS), with a hydride-containing oligomer / polymer, such as a silicon hydride-containing PDMS.

[0012] The term "alkenyl" refers to a monovalent group that is a radical of an alkene, which is a hydrocarbon having at least one carbon-carbon double bond. An alkenyl can be linear, branched, cyclic, or a combination thereof and typically contains 2 to 20 carbon atoms. In some embodiments, an alkenyl contains 2 to 18, 2 to 12, 2 to 10, 4 to 10, 4 to 8, 2 to 8, 2 to 6, or 2 to 4 carbon atoms. Exemplary alkenyl groups include ethenyl, n-propenyl, and n-butenyl.

[0013] The term "alkyl" refers to a monovalent group that is a radical of an alkane, which is a saturated hydrocarbon. An alkyl can be linear, branched, cyclic, or a combination thereof and typically has 1 to 20 carbon atoms. In some embodiments, an alkyl group contains 1 to 18, 1 to 12, 1 to 10, 1 to 8, 1 to 6, or 1 to 4 carbon atoms. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, cyclohexyl, n-heptyl, n-octyl, and ethylhexyl.

[0014] The term "alkylene" refers to a divalent group that is a radical of an alkane. Alkylene may be linear, branched, cyclic, or a combination thereof. Alkylene often has 1 to 20 carbon atoms. In some embodiments, alkylene contains 1 to 18, 1 to 12, 1 to 10, 1 to 8, 1 to 6, or 1 to 4 carbon atoms. The radical centers of the alkylene may be the same carbon atom (i.e., an alkylidene) or may be different carbon atoms.

[0015] The term "alkoxy" refers to a monovalent group of formula -OR where R is an alkyl group.

[0016] The term "alkoxycarbonyl" refers to a monovalent group of formula -(CO)OR where R is an alkyl group and (CO) denotes a carbonyl group where the carbon is attached to the oxygen with a double bond.

[0017] The term "aralkyl" refers to a group of the formula -R a -Ar, where R a is an alkylene and Ar is an aryl group, i.e., an aralkyl is an alkyl substituted with an aryl.

[0018] The term “aralkylene” has the formula: a -Ar a -[wherein, R a is alkylene, and Ar a refers to a divalent group in which the alkyl group is an arylene (i.e., an alkylene is bonded to an arylene).

[0019] The term "aryl" refers to a monovalent group that is aromatic and carbocyclic. An aryl can have 1 to 5 rings that are connected or fused to the aromatic ring. Other ring structures may be aromatic, non-aromatic, or combinations thereof. Examples of aryl groups include, but are not limited to, phenyl, biphenyl, terphenyl, anthryl, naphthyl, acenaphthyl, anthraquinonyl, phenanthryl, anthracenyl, pyrenyl, perylenyl, and fluorenyl.

[0020] The term "arylene" refers to a divalent group that is carbocyclic and aromatic. The group has 1 to 5 rings that are connected, fused, or a combination thereof. The other rings may be aromatic, non-aromatic, or a combination thereof. In some embodiments, the arylene group has up to 5 rings, up to 4 rings, up to 3 rings, up to 2 rings, or one aromatic ring. For example, the arylene group may be phenylene.

[0021] The term "aryloxy" refers to a monovalent group of formula -OAr where Ar is an aryl group.

[0022] The term "carbonyl" refers to a divalent group of formula -(CO)- where a carbon atom is attached with a double bond to an oxygen atom.

[0023] The term "halo" refers to fluoro, chloro, bromo, or iodo.

[0024] The term "haloalkyl" refers to an alkyl in which at least one hydrogen atom is replaced with halo. Some haloalkyl groups are fluoroalkyl, chloroalkyl, or bromoalkyl groups.

[0025] The term "heteroalkylene" refers to a divalent group that includes at least two alkylene groups connected by thio, oxy, or -NR-, where R is an alkyl. The heteroalkylene can be linear, branched, cyclic, or a combination thereof and can include up to 60 carbon atoms and up to 15 heteroatoms. In some embodiments, the heteroalkylene includes up to 50 carbon atoms, up to 40 carbon atoms, up to 30 carbon atoms, up to 20 carbon atoms, or up to 10 carbon atoms. Some heteroalkylenes are polyalkylene oxides, where the heteroatoms are oxygen.

[0026] The term "oxalyl" refers to a divalent group of formula -(CO)-(CO)-, where each (CO) denotes a carbonyl group.

[0027] The terms "oxalylamino" and "aminooxalyl" are used interchangeably and refer to a divalent group of formula -(CO)-(CO)-NH-, where each (CO) denotes a carbonyl.

[0028] The term "aminooxalylamino" means Formula -NH-(CO)-(CO)-NR d (wherein each (CO) represents a carbonyl group; R drefers to a divalent group of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, d is hydrogen or alkyl. In many embodiments, R d is hydrogen.

[0029] The terms "polymer" and "polymeric material" refer to both a material prepared from one type of monomer, such as a homopolymer, or a material prepared from two or more types of monomers, such as a copolymer, terpolymer, etc. Similarly, the term "polymerizing" refers to the process of making a polymeric material, which can be a homopolymer, copolymer, terpolymer, etc. The terms "copolymer" and "copolymeric material" refer to a polymeric material prepared from at least two types of monomers.

[0030] The term "polydiorganosiloxane" refers to a divalent segment of the formula [ka] In the formula, each R 1 are independently alkyl, haloalkyl, aralkyl, alkenyl, aryl, or aryl substituted with alkyl, alkoxy or halo; each Y is independently alkylene, aralkylene, or combinations thereof; and the subscript n is independently an integer from 40 to 1500.

[0031] The term "adjacent" means that a first layer is located near a second layer. The first layer may be in contact with the second layer or may be separated from the second layer by one or more additional layers.

[0032] The terms "room temperature" and "ambient temperature" are used interchangeably to mean a temperature in the range of 20°C to 25°C.

[0033] Unless otherwise indicated, all numbers expressing structural dimensions, quantities, and physical properties used in the specification and claims are understood to be modified in all instances by the term "about." Thus, unless indicated to the contrary, the recited numbers are approximations that may vary depending upon the desired properties using the teachings disclosed herein.

[0034] Adhesive Composition The present disclosure generally relates to adhesive articles that can be removed from a substrate, wall or surface (generally, an adherend) without damage. In currently preferred implementations described herein, the adhesive composition is peelable. In other implementations, the peelable layer is stretch-peelable. The resulting adhesive article can be attached or placed adjacent to a hardgood.

[0035] Adhesive articles comprising the adhesive compositions described herein provide excellent adhesion and shear retention during use, as well as damage-free removal from walls, surfaces, or substrates to which the adhesive article is adhered, attached, or attached. In embodiments featuring stretch-releasable adhesives, the article can be removed from a substrate or surface by stretching at an angle of less than 35°. In embodiments featuring peel-releasable (i.e., releasable) adhesives, the article is a single-layer or multi-layer structure that can be removed from a substrate or surface by stretching at an angle of 35° or more. In some embodiments, the releasable adhesive can be removed by a combination of stretching and peel-removal mechanisms.

[0036] As mentioned before, the present disclosure generally relates to adhesive articles that can be removed from substrates without damage. As used herein, terms such as "without damage" and "without damage" mean that the adhesive article can be separated from the substrate without causing visible damage and / or leaving residue on paint, coating, resin, covering, or the substrate that is under the substrate. Visible damage to the substrate can be, for example, in the form of scratches, tears, delamination, breakage, crumbling, distortion, blistering, bubbles, etc. of any layer of the substrate. Visible damage can also be discoloration, weakening, gloss change, haze change, or other changes in the appearance of the substrate.

[0037] The adhesive composition of the present disclosure comprises a silicone polymer, a tackifying resin, and a filler. The adhesive composition may be at least one of pressure-sensitive and heat-activated, as these terms are defined below. In some embodiments, the adhesive composition comprises at least one of (1) a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin, and an inorganic particulate filler, (2) a silicone polyurea block copolymer, a silicate tackifying resin, and an inorganic particulate filler, or an addition cure silicone, a silicate tackifying resin, and an inorganic particulate filler.

[0038] Silicone Polymer In some embodiments featuring a polydiorganosiloxane polyoxamide copolymer, the copolymer contains at least two repeat units of Formula I: [ka]

[0039] In this formula, each R 1 is independently alkyl, haloalkyl, aralkyl, alkenyl, aryl, or aryl substituted with alkyl, alkoxy, or halo; R 1At least 50 percent of the groups are methyl. Each Y is independently an alkylene, an aralkylene, or a combination thereof. The subscript n is independently an integer from 40 to 1500, and the subscript p is an integer from 1 to 10. The group G is a group of formula R 3 HN-G-NHR 3 From diamine, two -NHR 3 The R group is a divalent group that is a residue unit equal to the residue unit minus the R group. 3 is hydrogen or alkyl (e.g., alkyl having 1 to 10, 1 to 6, or 1 to 4 carbon atoms), or R 3 together with G and the nitrogen to which they are both attached form a heterocyclic group (e.g., R 3 HN-G-NHR 3 is piperazine, etc.). Each asterisk ( * ) indicates the site at which the repeat unit is attached to another group within the copolymer, such as another repeat unit of formula I.

[0040] R in Formula I 1 Suitable alkyl groups for R typically have 1 to 10, 1 to 6, or 1 to 4 carbon atoms. Exemplary alkyl groups include, but are not limited to, methyl, ethyl, isopropyl, n-propyl, n-butyl, and isobutyl. 1 Haloalkyl groups suitable for often have only a portion of the hydrogen atoms of the corresponding alkyl group replaced with halogen. Exemplary haloalkyl groups include chloroalkyl and fluoroalkyl groups having 1 to 3 halo atoms and 3 to 10 carbon atoms. 1 Alkenyl groups suitable for R often have 2 to 10 carbon atoms. Exemplary alkenyl groups such as ethenyl, n-propenyl, and n-butenyl often have 2 to 8, 2 to 6, or 2 to 4 carbon atoms. 1Suitable aryl groups for often have 6 to 12 carbon atoms. Phenyl is an exemplary aryl group. The aryl group can be unsubstituted or substituted with alkyl (e.g., alkyl having 1 to 10 carbon atoms, 1 to 6 carbon atoms, or 1 to 4 carbon atoms), alkoxy (e.g., alkoxy having 1 to 10 carbon atoms, 1 to 6 carbon atoms, or 1 to 4 carbon atoms), or halo (e.g., chloro, bromo, or fluoro). R 1 Suitable aralkyl groups for typically have an alkylene group having 1 to 10 carbon atoms and an aryl group having 6 to 12 carbon atoms. In some exemplary aralkyl groups, the aryl group is phenyl and the alkylene group has 1 to 10 carbon atoms, 1 to 6 carbon atoms, or 1 to 4 carbon atoms (i.e., the structure of the aralkyl is alkylene-phenyl, where the alkylene is attached to the phenyl group).

[0041] In some embodiments, R 1 At least 50 percent of the groups are methyl. For example, R 1 At least 60 percent, at least 70 percent, at least 80 percent, at least 90 percent, at least 95 percent, at least 98 percent, or at least 99 percent of the groups may be methyl. 1 The groups may be selected from alkyl having at least 2 carbon atoms, haloalkyl, aralkyl, alkenyl, aryl, or aryl substituted with alkyl, alkoxy or halo.

[0042] Each Y in formula I is independently an alkylene, an aralkylene, or a combination thereof. Suitable alkylene groups typically have up to 10 carbon atoms, up to 8 carbon atoms, up to 6 carbon atoms, or up to 4 carbon atoms. Exemplary alkylene groups include methylene, ethylene, propylene, and butylene. Suitable aralkylene groups typically have an arylene group having 6 to 12 carbon atoms bonded to an alkylene group having 1 to 10 carbon atoms. In some exemplary aralkylene groups, the arylene moiety is phenylene. That is, the divalent aralkylene group is a phenylene-alkylene, where the phenylene is bonded to an alkylene having 1 to 10, 1 to 8, 1 to 6, or 1 to 4 carbon atoms. As used herein, with respect to the Y group, "combinations thereof" refers to a combination of two or more groups selected from alkylene groups and aralkylene groups. For example, the combination can be a single aralkylene bonded to a single alkylene (e.g., alkylene-arylene-alkylene). In one exemplary alkylene-arylene-alkylene combination, the arylene is phenylene and each alkylene has 1 to 10, 1 to 6, or 1 to 4 carbon atoms.

[0043] Each subscript n in formula I is independently an integer between 40 and 1500. For example, subscript n can be an integer between 1000, 500, 400, 300, 200, 100, 80, or 60. The value of n is often at least 40, at least 45, at least 50, or at least 55. For example, subscript n can be in the range of 40 to 1000, 40 to 500, 50 to 500, 50 to 400, 50 to 300, 50 to 200, 50 to 100, 50 to 80, or 50 to 60.

[0044] The subscript p is an integer from 1 to 10. For example, the value of p is often an integer at most 9, at most 8, at most 7, at most 6, at most 5, at most 4, at most 3, or at most 2. The value of p can be in the range of 1 to 8, 1 to 6, or 1 to 4.

[0045] The group G in formula I is of the formula R 3 HN-G-NHR 3 From the diamine compound, two amino groups (i.e., -NHR 3 The residue unit is equivalent to the residue obtained by removing the group R. 3 is hydrogen or alkyl (e.g., alkyl having 1 to 10, 1 to 6, or 1 to 4 carbon atoms), or R 3 together with G and the nitrogen to which they are both attached form a heterocyclic group (e.g., R 3 HN-G-NHR 3 is piperazine). The diamine may have primary or secondary amino groups. In most embodiments, R 3 is hydrogen or alkyl. In many embodiments, both of the amino groups of the diamine are primary amino groups (i.e., R 3 The groups are both hydrogen), and the diamine is of the formula H2N-G-NH2.

[0046] In some embodiments, G is an alkylene, heteroalkylene, polydiorganosiloxane, arylene, aralkylene, or combinations thereof. Suitable alkylenes often have 2 to 10, 2 to 6, or 2 to 4 carbon atoms. Exemplary alkylene groups include ethylene, propylene, butylene, and the like. Suitable heteroalkylenes often are polyoxyalkylenes, such as polyoxyethylenes having at least two ethylene units, polyoxypropylenes having at least two propylene units, or copolymers thereof. Suitable polydiorganosiloxanes include the polydiorganosiloxane diamines of formula III described below minus two amino groups. Exemplary polydiorganosiloxanes include, but are not limited to, polydimethylsiloxanes having alkylene Y groups. Suitable aralkylene groups typically contain an arylene group having 6 to 12 carbon atoms bonded to an alkylene group having 1 to 10 carbon atoms. Some exemplary aralkylene groups are phenylene-alkylene, where the phenylene is bonded to an alkylene having 1 to 10 carbon atoms, 1 to 8 carbon atoms, 1 to 6 carbon atoms, or 1 to 4 carbon atoms. As used herein, "combinations thereof" with respect to the group G refers to a combination of two or more groups selected from alkylene, heteroalkylene, polydiorganosiloxane, arylene, and aralkylene. The combination may be, for example, an aralkylene bonded to an alkylene (e.g., alkylene-arylene-alkylene). In one exemplary alkylene-arylene-alkylene combination, the arylene is phenylene, and each alkylene has 1 to 10, 1 to 6, or 1 to 4 carbon atoms.

[0047] In some embodiments, the polydiorganosiloxane polyoxamide has the formula -R a -(CO)-NH-(wherein, R ais alkylene). Every carbonylamino group along the backbone of the copolymer material is part of an oxalylamino group (i.e., a -(CO)-(CO)-NH- group). That is, every carbonyl group along the backbone of the copolymer material is bonded to another carbonyl group and is part of an oxalyl group. More specifically, polydiorganosiloxane polyoxamides have multiple aminooxalylamino groups.

[0048] In some embodiments, the polydiorganosiloxane polyoxamide can be a linear block copolymer and an elastomeric material.Unlike many known polydiorganosiloxane polyamides, which are generally formulated as brittle solids or hard plastics, the polydiorganosiloxane polyoxamide can be formulated to contain more than 50 weight percent of polydiorganosiloxane segments, based on the weight of the copolymer.The weight percent of diorganosiloxane in the polydiorganosiloxane polyoxamide can be increased by using higher molecular weight polydiorganosiloxane segments, providing more than 60 weight percent, more than 70 weight percent, more than 80 weight percent, more than 90 weight percent, more than 95 weight percent, or more than 98 weight percent of polydiorganosiloxane segments in the polydiorganosiloxane polyoxamide. By using higher amounts of polydiorganosiloxane, elastomeric materials can be prepared that have a lower modulus while still maintaining adequate strength.

[0049] Some of the polydiorganosiloxane polyoxamides can be heated to temperatures of up to 200°C, up to 225°C, up to 250°C, up to 275°C, or up to 300°C without significant degradation of the material. For example, when heated in a thermogravimetric analyzer in the presence of air, the copolymers often have a loss of less than 10 weight percent when scanned at a rate of 50°C / min over the range of 20°C to about 350°C. Furthermore, the copolymers can often be heated in air at a temperature of, for example, 250°C for one hour without appreciable degradation, as evidenced by no detectable loss in mechanical strength upon cooling.

[0050] Polydiorganosiloxane polyoxamide copolymers have many of the desirable properties of polysiloxanes, such as low glass transition temperatures, thermal and oxidative stability, UV resistance, low surface energy and hydrophobicity, and high permeability to many gases. In addition, the copolymers exhibit good to excellent mechanical strength.

[0051] The copolymer material of formula I may be optically transparent. As used herein, the term "optically transparent" refers to a material that appears transparent to the human eye. Optically transparent copolymer materials often have a luminous transmittance of at least about 90 percent, a haze of less than about 2 percent, and an opacity of less than about 1% in the wavelength range of 400 nm to 700 nm. Both the luminous transmittance and the haze can be measured, for example, using the method of ASTM-D 1003-95.

[0052] Additionally, the copolymer material of formula I can have a low refractive index. As used herein, the term "refractive index" refers to the absolute refractive index of a material (e.g., a copolymer material or an adhesive composition), which is the ratio of the electromagnetic radiation velocity in free space to the electromagnetic radiation velocity in the material of interest. The electromagnetic radiation is white light. The refractive index is measured using, for example, an Abbe refractometer available from Fisher Instruments (Pittsburgh, PA). The measurement of the refractive index can vary to some extent depending on the specific refractometer used. The copolymer material typically has a refractive index within the range of about 1.41 to about 1.50.

[0053] The polydiorganosiloxane polyoxamides are soluble in many common organic solvents, such as, for example, toluene, tetrahydrofuran, dichloromethane, aliphatic hydrocarbons (eg, alkanes such as hexane), or mixtures thereof.

[0054] Linear block copolymers having repeating units of Formula I can be prepared, for example, as shown in Reaction Scheme A. [ka]

[0055] In this reaction scheme, a precursor of formula II is mixed under reaction conditions with a diamine having two primary amino groups, two secondary amino groups, or one primary and one secondary amino group. The diamine is typically a compound of formula R 3 HN-G-NHR 3 R 2 The OH by-product is typically removed from the resulting polydiorganosiloxane polyoxamide.

[0056] Diamine R in Reaction Scheme A 3 HN-G-NHR 3 is a cyclic amine having two amino groups (i.e., -NHR 3 ) The group R 3is hydrogen or alkyl (e.g., alkyl having 1 to 10, 1 to 6, or 1 to 4 carbon atoms), or R 3 R, taken together with G and the nitrogen to which they are both attached, forms a heterocyclic group (e.g., diamines are piperazines, etc.). In most embodiments, R 3 is hydrogen or alkyl. In many embodiments, the diamine has two primary amino groups (i.e., each R 3 The groups are hydrogen), and the diamine is of the formula H2N-G-NH2. The portion of the diamine not including the two amino groups is referred to as group G in formula I.

[0057] The diamines are sometimes classified as organic diamines or polydiorganosiloxane diamines, and the organic diamines include, for example, those selected from alkylenediamines, heteroalkylenediamines, arylenediamines, aralkylenediamines, or alkylene-aralkylenediamines. The diamines have only two amino groups, and the resulting polydiorganosiloxane polyoxamides are linear block copolymers that are often elastomeric, hot melt processable (e.g., the copolymers can be processed at temperatures up to 250°C or higher without appreciable degradation of the composition), and soluble in some common organic solvents. The diamines do not have polyamines with more than two primary or secondary amino groups. Tertiary amines that do not react with the precursor of formula II can be present. Additionally, the diamines do not have any carbonyl amino groups. That is, the diamines are not amides.

[0058] Exemplary polyoxyalkylene diamines (i.e., G is a heteroalkylene where the heteroatom is oxygen) include those available from Huntsman (The Woodlands, TX) under the tradenames JEFFAMINE D-230 (i.e., a polyoxypropylene diamine having an average molecular weight of about 230 g / mol), JEFFAMINE D-400 (i.e., a polyoxypropylene diamine having an average molecular weight of about 400 g / mol), JEFFAMINE D-2000 (i.e., a polyoxypropylene diamine having an average molecular weight of about 2,000 g / mol), JEFFAMINE HK-511 (i.e., a polyether diamine having both oxyethylene and oxypropylene groups and an average molecular weight of about 220 g / mol), JEFFAMINE ED-2003 (i.e., a polyethylene glycol endcapped with polypropylene oxide having an average molecular weight of about 2,000 g / mol), and JEFFAMINE ED-2003 (i.e., a polyethylene glycol endcapped with polypropylene oxide having an average molecular weight of about 2,000 g / mol). Examples include, but are not limited to, those commercially available under the name EDR-148 (i.e., triethylene glycol diamine).

[0059] Exemplary alkylenediamines (i.e., G is alkylene) include, but are not limited to, ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, 2-methylpentamethylene-1,5-diamine (i.e., commercially available from DuPont, Wilmington, Del. under the trademark DYTEK A), 1,3-pentanediamine (commercially available from DuPont under the trademark DYTEK EP), 1,4-cyclohexanediamine, 1,2-cyclohexanediamine (commercially available from DuPont under the trademark DHC-99), 4,4′-bis(aminocyclohexyl)methane, and 3-aminomethyl-3,5,5-trimethylcyclohexylamine.

[0060] Exemplary arylene diamines (i.e., G is an arylene, such as phenylene) include, but are not limited to, m-phenylene diamine, o-phenylene diamine, and p-phenylene diamine. Exemplary aralkylene diamines (i.e., G is an aralkylene, such as alkylene-phenyl) include, but are not limited to, 4-aminomethyl-phenylamine, 3-aminomethyl-phenylamine, and 2-aminomethyl-phenylamine. Exemplary alkylene-aralkylene diamines (i.e., G is an alkylene-aralkylene, such as alkylene-phenylene-alkylene) include, but are not limited to, 4-aminomethyl-benzylamine, 3-aminomethyl-benzylamine, and 2-aminomethyl-benzylamine.

[0061] The precursor of formula II in Reaction Scheme A has at least one polydiorganosiloxane segment and at least two oxalylamino groups. 1 , the group Y, the subscript n, and the subscript p are the same as described for formula I. 2 is independently alkyl, haloalkyl, aryl, or aryl substituted with alkyl, alkoxy, halo, or alkoxycarbonyl.

[0062] R 2Suitable alkyl and haloalkyl groups for often have 1-10, 1-6, or 1-4 carbon atoms. Tertiary alkyl (e.g., tert-butyl) and haloalkyl groups can be used, but often there is a primary or secondary carbon atom directly bonded (i.e., attached) to the adjacent oxy group. Exemplary alkyl groups include methyl, ethyl, n-propyl, iso-propyl, n-butyl, and iso-butyl. Exemplary haloalkyl groups include chloroalkyl and fluoroalkyl groups, in which some, but not all, of the hydrogen atoms on the corresponding alkyl group are replaced with halo atoms. For example, the chloroalkyl or fluoroalkyl group can be chloromethyl, 2-chloroethyl, 2,2,2-trichloroethyl, 3-chloropropyl, 4-chlorobutyl, fluoromethyl, 2-fluoroethyl, 2,2,2-trifluoroethyl, 3-fluoropropyl, 4-fluorobutyl, and the like. R 2 Suitable aryl groups for include those having 6 to 12 carbon atoms, such as phenyl. The aryl group can be unsubstituted or substituted with alkyl (e.g., alkyl having 1 to 4 carbon atoms, such as methyl, ethyl, or n-propyl), alkoxy (e.g., alkoxy having 1 to 4 carbon atoms, such as methoxy, ethoxy, or propoxy), halo (e.g., chloro, bromo, or fluoro), or alkoxycarbonyl (e.g., alkoxycarbonyl having 2 to 5 carbon atoms, such as methoxycarbonyl, ethoxycarbonyl, or propoxycarbonyl).

[0063] The precursor of formula II can include a single compound (i.e., all of the compounds have the same values ​​for p and n) or multiple compounds (i.e., the compounds have different values ​​for p, different values ​​for n, or different values ​​for both p and n). Precursors with different n values ​​have siloxane chains of different lengths. Precursors with a p value of at least 2 are chain extended. Different amounts of chain-extended precursors of formula II in the mixture can affect the final properties of the elastomeric material of formula I. That is, the amount of the second compound of formula II (i.e., p is at least equal to 2) can be advantageously varied to provide elastomeric materials with different properties. For example, a higher amount of the second compound of formula II can modify the melt rheology (e.g., make the elastomeric material flow more easily when melted), modify the flexibility of the elastomeric material, reduce the modulus of the elastomeric material, or a combination thereof.

[0064] In some embodiments, the precursor is a mixture of a first compound of formula II with subscript p equal to 1 and a second compound of formula II with subscript p equal to at least 2. The first compound can include a plurality of different compounds with different values ​​of n. The second compound can include a plurality of compounds with different values ​​of p, different values ​​of n, or different values ​​of both p and n. The mixture can include at least 50 weight percent of the first compound of formula II (i.e., p equal to 1) and 50 weight percent or less of the second compound of formula II (i.e., p equal to at least 2), based on the total weight of the first and second compounds in the mixture. In some mixtures, the first compound is present in an amount of at least 55 weight percent, at least 60 weight percent, at least 65 weight percent, at least 70 weight percent, at least 75 weight percent, at least 80 weight percent, at least 85 weight percent, at least 90 weight percent, at least 95 weight percent, or at least 98 weight percent, based on the total amount of the compounds of formula II. The mixture often contains no more than 50 weight percent, no more than 45 weight percent, no more than 40 weight percent, no more than 35 weight percent, no more than 30 weight percent, no more than 25 weight percent, no more than 20 weight percent, no more than 15 weight percent, no more than 10 weight percent, no more than 5 weight percent, or no more than 2 weight percent of the second compound.

[0065] Reaction Scheme A can be carried out using multiple precursors having formula II, multiple diamines, or combinations thereof. Multiple precursors having different average molecular weights can be mixed with a single diamine or multiple diamines under reaction conditions. For example, a precursor of formula II can include a mixture of materials having different values ​​of n, different values ​​of p, or different values ​​of both n and p. Multiple diamines can include, for example, a first diamine that is an organic diamine and a second diamine that is a polydiorganosiloxane diamine. Similarly, a single precursor can be mixed with multiple diamines under reaction conditions.

[0066] The molar ratio of the precursor of formula II to the diamine is often about 1:1. For example, the molar ratio is often 1:0.90 or less, 1:0.92 or less, 1:0.95 or less, 1:0.98 or less, or 1:1 or less. The molar ratio is often 1:1.02 or more, 1:1.05 or more, 1:1.08 or more, or 1:1.10 or more. For example, the molar ratio can be in the range of 1:0.90 to 1:1.10, 1:0.92 to 1:1.08, 1:0.95 to 1:1.05, or 1:0.98 to 1:1.02. For example, varying the molar ratio can be used to change the overall molecular weight, which can affect the rheology of the resulting copolymer. Additionally, the molar ratio can be varied to provide oxalylamino-containing end groups or amino end groups, depending on which reactant is present in molar excess.

[0067] The condensation reaction of the precursor of Formula II with the diamine (i.e., Reaction Scheme A) is often carried out at an elevated temperature, such as room temperature or a temperature of up to about 250° C. For example, the reaction can often be carried out at room temperature or a temperature of up to about 100° C. In other examples, the reaction can be carried out at a temperature of at least 100° C., at least 120° C., or at least 150° C. For example, the reaction temperature is often in the range of 100° C. to 220° C., in the range of 120° C. to 220° C., or in the range of 150° C. to 200° C. The condensation reaction is often complete in less than 1 hour, less than 2 hours, less than 4 hours, less than 8 hours, or less than 12 hours.

[0068] Reaction Scheme A can occur in the presence or absence of a solvent. A suitable solvent typically does not react with any reactants or products of the reaction. Furthermore, a suitable solvent typically allows all reactants and all products to be kept in solution at all times during the polymerization process. Exemplary solvents include, but are not limited to, toluene, tetrahydrofuran, dichloromethane, aliphatic hydrocarbons (e.g., alkanes such as hexane), or mixtures thereof.

[0069] Any solvent present can be stripped from the resulting polydiorganosiloxane polyoxamide at the end of the reaction. Solvents that can be removed under the same conditions used to strip the alcohol by-product are often preferred. The stripping process is often carried out at a temperature of at least 100°C, at least 125°C, or at least 150°C. The stripping process is typically at a temperature of less than 300°C, less than 250°C, or less than 225°C.

[0070] Volatile by-products, R 2 Since only the OH needs to be removed at the end of the reaction, it may be desirable to carry out Reaction Scheme A in the absence of a solvent. Furthermore, in solvents that are not compatible with both the reactants and the products, the reaction will not go to completion and the degree of polymerization will be low.

[0071] Any suitable reactor or process can be used to prepare the copolymer material according to Reaction Scheme A. The reaction can be carried out using a batch process, a semi-batch process, or a continuous process. An exemplary batch process can be carried out in a reaction vessel equipped with a mechanical agitator, such as a Brabender mixer, provided that the reaction product is in a molten state and has a low enough viscosity to be removed from the reactor. An exemplary semi-batch process can be carried out in a continuously stirred tube, tank, or fluidized bed. An exemplary continuous process can be carried out in a twin screw extruder, such as a single screw or wiped surface counter-rotating or co-rotating twin screw extruder.

[0072] In many processes, the components are metered and then mixed together to form a reaction mixture. The components can be metered volumetrically or gravimetrically, for example, using gears, pistons, or progressing cavity pumps. The components can be mixed using any known static or dynamic method, such as, for example, a static mixer, or a compounding mixer, such as a single or multiple screw extruder. The reaction mixture can then be formed, poured, pumped, coated, injection molded, sprayed, sputtered, atomized, stranded or sheeted, and partially or fully polymerized. The partially or fully polymerized material can then be optionally converted into particles, droplets, pellets, spheres, strands, ribbons, rods, tubes, films, sheets, coextruded films, webs, nonwovens, microreplicated structures, or other continuous or discrete shapes before conversion to a solid polymer. Any of these steps can be performed with or without the application of heat. In one exemplary process, the components can be metered using a gear pump, mixed using a static mixer, and injected into a mold prior to solidifying the polymerized material.

[0073] The polydiorganosiloxane-containing precursor having Formula II in Reaction Scheme A can be prepared by any known method. In some embodiments, the precursor is prepared by Reaction Scheme B. [ka]

[0074] A polydiorganosiloxane diamine of formula III (p moles) is reacted with a molar excess of an oxalate of formula IV (greater than p+1 moles) under an inert atmosphere to produce a polydiorganosiloxane-containing precursor of formula II and R 2 In this reaction, R 1 , Y, n, and p are the same as previously described for Formula I. Each R 2is independently alkyl, haloalkyl, aryl, or aryl substituted with alkyl, alkoxy, halo, or alkoxycarbonyl. The preparation of precursors of Formula II according to Reaction Scheme B is further described in U.S. Patent Application Publication No. 2007 / 0149745 (Leir et al.).

[0075] The polydiorganosiloxane diamine of formula III in Reaction Scheme B can be prepared by any known method and can have any suitable molecular weight, such as an average molecular weight ranging from 700 to 150,000 grams / mol. Suitable polydiorganosiloxane diamines and methods for making polydiorganosiloxane diamines are described, for example, in U.S. Pat. Nos. 3,890,269 (Martin), 4,661,577 (Jo Lane et al.), 5,026,890 (Webb et al.), 5,276,122 (Aoki et al.), 5,214,119 (Leir et al.), 5,461,134 (Leir et al.), 5,512,650 (Leir et al.), and 6,355,759 (Sherman et al.), which are incorporated herein by reference in their entireties. Several polydiorganosiloxane diamines are commercially available, for example, from Shin Etsu Silicones of America, Inc. (Torrance, Calif.) and Gelest Inc. (Morrisville, Pa.).

[0076] Polydiorganosiloxane diamines having molecular weights of greater than 2,000 g / mol or greater than 5,000 g / mol can be prepared using the methods described in U.S. Patents 5,214,119 (Leir et al.), 5,461,134 (Leir et al.), and 5,512,650 (Leir et al.). One of the methods described comprises reacting, under reactive conditions and an inert atmosphere, (a) a compound of the formula: [ka] (Wherein, Y and R 1is the same as defined for formula I), (b) sufficient cyclic siloxane to react with the amine functional endblocker to form a polydiorganosiloxane diamine having a molecular weight of less than 2,000 g / mol, and (c) an anhydrous aminoalkyl silanolate catalyst of the formula: [ka] (Wherein, Y and R 1 is the same as defined in formula I, M + is a sodium ion, a potassium ion, a cesium ion, a rubidium ion, or a tetramethylammonium ion). The reaction continues until substantially all of the amine functional endblocking agent is consumed, after which additional cyclic siloxane is added to increase the molecular weight. The additional cyclic siloxane is often added slowly (e.g., dropwise). The reaction temperature is often in the range of 80° C. to 90° C., and is carried out for a reaction time of 5 to 7 hours. The resulting polydiorganosiloxane diamine can be of high purity (e.g., less than 2 weight percent, less than 1.5 weight percent, less than 1 weight percent, less than 0.5 weight percent, less than 0.1 weight percent, less than 0.05 weight percent, or less than 0.01 weight percent silanol impurities). By varying the ratio of amine functional endblocking agent to cyclic siloxane, the molecular weight of the resulting polydiorganosiloxane diamine of formula III can be varied.

[0077] Another method for preparing the polydiorganosiloxane diamine of formula III includes reacting under reactive conditions and in an inert environment (a) an amine functional endblocking agent of the formula: [ka] (In the formula, R 1and Y are the same as described for formula I, and the subscript x is equal to an integer between 1 and 150, (b) sufficient cyclic siloxane to provide a polydiorganosiloxane diamine having an average molecular weight greater than the average molecular weight of the amine-functional endblocker, and (c) a catalyst selected from cesium hydroxide, cesium silanolate, rubidium silanolate, cesium polysiloxanolate, rubidium polysiloxanolate, and mixtures thereof. The reaction continues until substantially all of the amine-functional endblocker is consumed. This method is further described in U.S. Pat. No. 6,355,759 (B1) (Sherman et al.). Using this procedure, polydiorganosiloxane diamines of any molecular weight can be prepared.

[0078] Yet another method for preparing polydiorganosiloxane diamines of formula III is described in U.S. Patent No. 6,531,620 (B2) (Brader et al.) in which a cyclic silazane is reacted with a siloxane material having hydroxy end groups, as shown in the following reaction: [ka]

[0079] base R 1 and Y are the same as described for formula I. The subscript m is an integer greater than 1.

[0080] In Reaction Scheme B, the oxalate of formula IV is reacted with the polydiorganosiloxane diamine of formula III under an inert atmosphere. 2 The groups may be the same or different. In some methods, the two R 2 The groups are different and have different reactivities with the polydiorganosiloxane diamine of Formula III in Reaction Scheme B.

[0081] The oxalate of formula IV in Reaction Scheme B can be, for example, a compound of formula R 2It can be prepared by reacting an alcohol of -OH with oxalyl dichloride. Commercially available oxalates of formula IV (e.g., from Sigma-Aldrich (Milwaukee, WI) and VWR International (Bristol, CT)) include, but are not limited to, dimethyl oxalate, diethyl oxalate, di-n-butyl oxalate, di-tert-butyl-oxalate, bis(phenyl)oxalate, bis(pentafluorophenyl)oxalate, 1-(2,6-difluorophenyl)-2-(2,3,4,5,6-pentachlorophenyl)oxalate, and bis(2,4,6-trichlorophenyl)oxalate.

[0082] A molar excess of oxalate is used in Reaction Scheme B. That is, the molar ratio of oxalate to polydiorganosiloxane diamine is greater than the stoichiometric molar ratio, which is (p+1):p. This molar ratio is often greater than 2:1, greater than 3:1, greater than 4:1, or greater than 6:1. The condensation reaction usually occurs under an inert atmosphere and at room temperature when the components are mixed.

[0083] The condensation reaction used to generate the precursor of formula II (i.e., Reaction Scheme B) can occur in the presence or absence of a solvent. In some methods, the reaction mixture contains no solvent or only a small amount of solvent. In other methods, the solvent may include, for example, toluene, tetrahydrofuran, dichloromethane, or aliphatic hydrocarbons (e.g., alkanes such as hexane).

[0084] By removing excess oxalate from the precursor of formula II prior to reaction with the diamine in reaction scheme A, optically clear polydiorganosiloxane polyoxamides tend to be successfully formed. Excess oxalate can typically be removed from the precursor using a stripping process. For example, the reacted mixture (i.e., the product of the condensation reaction according to reaction scheme B) can be heated to a temperature of up to 150°C, up to 175°C, up to 200°C, up to 225°C, or up to 250°C to volatilize the excess oxalate. A vacuum can be applied to reduce the temperature required to remove the excess oxalate. The precursor compounds of formula II tend to show little or no appreciable decomposition at temperatures ranging from 200°C to 250°C or higher. Any other known method of removing excess oxalate can be used.

[0085] The by-product of the condensation reaction shown in Reaction Scheme B is an alcohol (i.e., R 2 -OH is an alcohol). The group R 2 is often limited to alkyl having 1-4 carbon atoms, haloalkyl having 1-4 carbon atoms, or aryl such as phenyl, which form an alcohol that can be easily removed (e.g., evaporated) by heating at a temperature of about 250° C. or less. Such alcohols can be removed when the reacted mixture is heated to a temperature sufficient to remove excess oxalate of formula IV.

[0086] Another useful class of silicone polymers is silicone polyurea block copolymers. Silicone polyurea block copolymers include the reaction product of polydiorganosiloxane diamines (also called silicone diamines), diisocyanates, and optionally organic polyamines. Suitable silicone polyurea block copolymers are represented by the repeating units shown and described in International Publication No. WO2016106040 (Sherman et al.): [ka] wherein each R independently preferably has from about 1 to 12 carbon atoms and is, for example, a trifluoroalkyl or vinyl group, a vinyl radical or a higher alkenyl radical, preferably of the formula R 2 (CH2) b - or -CH2) c CH=CH2 (wherein, R 2 is -(CH2) b --or-CH2) cNo. 5,236,997 (Fujiki), and U.S. Pat. No. 4,900,474 (Terae et al.) and U.S. Pat. No. 5,118,775 (Inomata et al.), and Perfluoroether-containing groups incorporated herein, preferably at least 50% of the R moieties are methyl radicals, with the remainder being monovalent alkyl or substituted alkyl radicals having 1 to 12 carbon atoms, alkenylene radicals, phenyl radicals, or substituted phenyl radicals, and each Z is a polyvalent radical that is preferably an arylene or aralkylene radical having from about 6 to 20 carbon atoms, an alkylene or cycloalkylene radical having from about 6 to 20 carbon atoms, and preferably Z is 2,6-tolylene, 4,4'-methylenediphenylene, 3,3'-dimethoxy-4,4'-biphenylene, tetramethyl-m-xylene, 4,4'-methylenedicyclohexylene, 3,5,5-trimethyl-3-methylenecyclohexylene, 1,6-hexamethylene, 1,4-cyclohexylene, 2,2,4-trimethylhexylene and mixtures thereof, each Y is independently a polyvalent radical which is an alkylene radical of 1 to 10 carbon atoms, preferably an aralkylene radical or an arylene radical having 6 to 20 carbon atoms, each D is selected from the group consisting of hydrogen, an alkyl radical of 1 to 10 carbon atoms, phenyl, and a radical completing a ring structure with B or Y to form a heterocycle, B is a polyvalent radical selected from the group consisting of alkylene, aralkylene, cycloalkylene, phenylene, polyalkylene oxides including, for example, polyethylene oxide, polypropylene oxide, polytetramethylene oxide, and copolymers and mixtures thereof, m is a number from 0 to about 1000, n is a number that is at least 1, and p is a number that is at least 10, preferably from about 15 to about 2000, and more preferably from 30 to 1500.

[0087] Useful silicone polyurea block copolymers are disclosed, for example, in U.S. Pat. Nos. 5,512,650, 5,214,119, and 5,461,134, WO 96 / 35458, WO 98 / 17726, WO 96 / 34028, WO 96 / 34030, and WO 97 / 40103, each of which is incorporated herein by reference.

[0088] Examples of useful silicone diamines for use in preparing the silicone polyurea block copolymers include the polydiorganosiloxane diamines represented by the formula shown and described in U.S. Pat. No. 8,334,037 (Sheridan et al.): [ka] wherein R, Y, D, and p are each defined as above. Preferably, the polydiorganosiloxane diamine has a number average molecular weight of greater than about 700.

[0089] Useful polydiorganosiloxane diamines include any polydiorganosiloxane diamines included in formula IX above, including polydiorganosiloxane diamines having a molecular weight in the range of about 700 to 150,000, preferably about 10,000 to about 60,000, more preferably about 25,000 to about 50,000. Suitable polydiorganosiloxane diamines and methods for making polydiorganosiloxane diamines are disclosed, for example, in U.S. Patent Nos. 3,890,269, 4,661,577, 5,026,890, and 5,276,122, WO 95 / 03354 and WO 96 / 35458, each of which is incorporated herein by reference.

[0090] Examples of useful polydiorganosiloxane diamines include polydimethylsiloxane diamine, polydiphenylsiloxane diamine, polytrifluoropropylmethylsiloxane diamine, polyphenylmethylsiloxane diamine, polydiethylsiloxane diamine, polydivinylsiloxane diamine, polyvinylmethylsiloxane diamine, poly(5-hexenyl)methylsiloxane diamine, and combinations and copolymers thereof.

[0091] Suitable polydiorganosiloxane diamines are commercially available, for example, from Shin Etsu Silicones of America, Inc. (Torrance, Calif.) and Huls America, Inc. Preferably, the polydiorganosiloxane diamines are substantially pure and prepared as disclosed in U.S. Pat. No. 5,214,119 and incorporated herein. Such high purity polydiorganosiloxane diamines are prepared from the reaction of cyclic organosilanes with bis(aminoalkyl)disiloxanes using anhydrous aminoalkyl functional silanolate catalysts, such as tetramethylammonium-3-aminopropyldimethylsilanolate, preferably in an amount of less than 0.15 weight percent based on the weight of the total amount of cyclic organosiloxanes if the reaction is carried out in two stages. Particularly preferred polydiorganosiloxane diamines are prepared using cesium and rubidium catalysts, as disclosed in U.S. Pat. No. 5,512,650 and incorporated herein.

[0092] The polydiorganosiloxane diamine component provides a means of adjusting the modulus of the resulting silicone polyurea block copolymer. Generally, higher molecular weight polydiorganosiloxane diamines result in copolymers with lower modulus, while lower molecular weight polydiorganosiloxane polyamines result in copolymers with higher modulus.

[0093] Examples of useful polyamines include polyoxyalkylene diamines, including those available commercially from Hunstman Corporation (Houston, Tex.) under the tradenames D-230, D-400, D-2000, D-4000, ED-2001, and EDR-148; polyoxyalkylene triamines, including those available commercially from Hunstman under the tradenames T-403, T-3000, and T-5000; and polyalkylenes, including those available from DuPont (Wilmington, Del.) under the tradenames Dytek A and Dytek EP.

[0094] The optional polyamine provides a means to modify the modulus of the copolymer. The concentration, type, and molecular weight of the organic polyamine affect the modulus of the silicone polyurea block copolymer.

[0095] The silicone polyurea block copolymer preferably contains the polyamine in an amount of about 3 moles or less, more preferably about 0.25 to about 2 moles. The polyamine preferably has a molecular weight of about 300 g / mol or less.

[0096] Any polyisocyanate, such as diisocyanates and triisocyanates, that can react with the above polyamines can be used in the preparation of the silicone polyurea block copolymer. Examples of suitable diisocyanates include aromatic diisocyanates, such as 2,6-toluene diisocyanate, 2,5-toluene diisocyanate, 2,4-toluene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, methylene bis(o-chlorophenyl diisocyanate), methylene diphenylene-4,4'-diisocyanate, polycarbodiimide modified methylene diphenylene diisocyanate, (4,4'-diisocyanato-3,3',5,5'-tetraethyl)diphenylmethane, 4,4'-diisocyanato-3,3'-dimethoxybiphenyl (o-dianisidine diisocyanate), 5-chloro-2,4-toluene diisocyanate, and and 1-chloromethyl-2,4-diisocyanatobenzene, aromatic-aliphatic diisocyanates such as m-xylylene diisocyanate and tetramethyl-m-xylylene diisocyanate, aliphatic diisocyanates such as 1,4-diisocyanatobutane, 1,6-diisocyanatohexane, 1,12-diisocyanatododecane, and 2-methyl-1,5-diisocyanatopentane, and alicyclic diisocyanates such as methylenedicyclohexylene-4,4'-diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate), and cyclohexylene-1,4-diisocyanate.

[0097] Any triisocyanate that can react with polyamines, especially polydiorganosiloxane diamines, is suitable.Examples of such triisocyanates include multifunctional isocyanates, isocyanurates, and adducts, such as those produced from biuret.Examples of commercially available polyisocyanates include those available from Bayer under the trade names DESMODUR and MONDUR, and some of the series of polyisocyanates available from Dow Plastics under the trade name PAPI.

[0098] The polyisocyanate is preferably present in a stoichiometric amount based on the amount of polydiorganosiloxane diamine and any optional polyamine.

[0099] Silicone polyurea block copolymers can be prepared by solvent-based processes, solventless processes, or combinations thereof. Useful solvent-based processes are described, for example, in Tyagi et al., "Segmented Organosiloxane Copolymers: 2. Thermal and Mechanical Properties of Siloxane-Urea Copolymers", Polymer, vol. 25, December, 1984, and U.S. Patent No. 5,214,119 (Leir et al.), which are incorporated herein by reference. Useful methods for preparing silicone polyurea block copolymers are also described, for example, in U.S. Patent Nos. 5,512,650, 5,214,119, 5,461,134, WO 96 / 35458, 98 / 17726, 96 / 34028, and 97 / 40103, which are incorporated herein by reference.

[0100] Other suitable silicone polymers for use in the adhesive composition include addition cure silicones, peroxide cure silicones, and moisture cure silicones. Silicone-containing polymers prepared by addition cure chemistry are generally polydiorganosiloxanes with alkenyl groups, SiO 4 / 2 and R3 SiOι / 2A copolymer silicone resin comprising structural units, where R has one or more of the following functional groups: silicone-bonded hydrogen, silicone-bonded alkenyl groups, such as those selected from the group consisting of vinyl, allyl, and propenyl, or silanol, as previously described, and optionally a crosslinker or chain extender, and a platinum or other noble metal hydrosilylation catalyst to effect cure of the silicone adhesive. One such polymer is formed by an addition cure reaction between vinyl-terminated poly(dimethylsiloxane) (PDMS) and hydrogen-terminated PDMS in the presence of a hydrosilylation catalyst (e.g., a platinum complex). The vinyl-terminated and hydrogen-terminated PDMS chains are referred to as "functionalized" silicones because of their particular chemical moieties. Individually, such functional silicones are generally not reactive, but together they can form reactive silicone systems. Exemplary hydrosilylation catalysts are described in U.S. Pat. No. 8,202,939 (Moore et al.). One exemplary suitable addition cure silicone is Sylgard 184, available from Dow Corning (Midland, Mich.).

[0101] Generally, peroxide cured silicones include, prior to curing, (i) a reaction adduct of polydimethylsiloxane and / or polydiphenylsiloxane gum and a silicone resin, (ii) optionally one or more silicone resins, and (iii) at least one peroxide crosslinker. In certain embodiments, such peroxide curing agents may abstract hydrogen and / or crosslink and require high temperatures. For example, benzoyl peroxide requires a curing temperature of more than 150° C. for the catalyst to function. An exemplary suitable peroxide curing agent is Luperox 101 available from Arkema Inc. (Houston, TX).

[0102] The silicone polymer is typically present in an amount of at least 20% by weight and no more than 80% by weight, based on the total weight of the adhesive composition, or any amount within that range. In certain implementations, it may be preferred for the silicone-containing polymer to be present in a concentration of at least 30% by weight and no more than 75% by weight, based on the total weight of the adhesive composition.

[0103] Tackifying Resin By combining silicone-containing polymers with silicate tackifying resins, either pressure-sensitive or heat-activated adhesives can be formulated.As used herein, the term "pressure-sensitive adhesive" refers to a material that is tacky, adheres under finger pressure, does not require activation by any energy source, and when applied to an adherend, has sufficient adhesion to hold on the adherend at the intended angle of use and intended load, and has sufficient adhesion to be removed cleanly from the adherend.As used herein, the term "heat-activated adhesive" refers to an adhesive composition that is essentially non-tacky at room temperature, but becomes tacky at a temperature above room temperature, e.g., above an activation temperature, such as above about 30°C.A heat-activated adhesive typically has the properties of a pressure-sensitive adhesive above the activation temperature.

[0104] Tackifying resins, such as silicate tackifying resins, are added to polydiorganosiloxane polyoxamide copolymers to provide or enhance the adhesive properties of the copolymer. The silicate tackifying resins can affect the physical properties of the resulting adhesive composition. For example, increasing the silicate tackifying resin content causes the adhesive composition to transition from a glassy to a rubbery state as the temperature increases. In some exemplary adhesive compositions, multiple silicate tackifying resins can be used to obtain desired performance.

[0105] Suitable silicate tackifying resins include those having the following structural unit M (i.e., monovalent R'SiO 1 / 2 unit), D (i.e., divalent R'2SiO 2 / 2 units), T (i.e., trivalent R'SiO 3 / 2units) and Q (i.e., tetravalent SiO 4 / 2 units), and combinations thereof. Typical exemplary silicate resins include MQ silicate tackifying resins, MQD silicate tackifying resins, and MQT silicate tackifying resins. These silicate tackifying resins usually have a number average molecular weight in the range of 100 to 50,000, or 500 to 15,000, and generally have methyl R' groups.

[0106] MQ silicate tackifier resin is R3SiO 1 / 2 Units ("M" units) and SiO 4 / 2 units ("Q" units), where the M units are bonded to Q units, each of which is bonded to at least one other Q unit. 4 / 2 The unit (the "Q" unit) is bonded to a hydroxyl group to form HOSiO 3 / 2 Units ("T OH " units), which corresponds to the silicon-bonded hydroxyl content of the silicate tackifying resin, while others 4 / 2 Some are only attached to units.

[0107] Such resins are described, for example, in Encyclopedia of Polymer Science and Engineering, vol. 15, John Wiley & Sons, New York, (1989), pp. 265-270, and in U.S. Pat. Nos. 2,676,182 (Daudt et al.), 3,627,851 (Brady), 3,772,247 (Flannigan), and 5,248,739 (Schmidt et al.). Other examples are disclosed in U.S. Pat. No. 5,082,706 (Tangney). The above resins are generally prepared in a solvent. Dry or solvent-free M silicone tackifying resins can be prepared as described in U.S. Pat. Nos. 5,319,040 (Wengrovius et al.), 5,302,685 (Tsumura et al.), and 4,935,484 (Wolfgruber et al.).

[0108] Certain MQ silicate tackifying resins can be prepared by the silica hydrosol endcapping process described in U.S. Patent No. 2,676,182 (Daudt et al.) and improved by U.S. Patent No. 3,627,851 (Brady) and U.S. Patent No. 3,772,247 (Flannigan). These improved processes often involve limiting the concentration of the sodium silicate solution, and / or the ratio of silicon to sodium in the sodium silicate, and / or the time before capping the neutralized sodium silicate solution, to values ​​generally lower than those disclosed by Daudt et al. Neutralized silica hydrosols are often stabilized with an alcohol, such as 2-propanol, to produce RSiO 1 / 2 The siloxane units are capped as soon as possible after neutralization. The level of silicon-bonded hydroxyl groups (i.e., silanols) on the MQ resin can be reduced to 1.5 weight percent or less, 1.2 weight percent or less, 1.0 weight percent or less, or 0.8 weight percent or less, based on the weight of the silicate tackifying resin. This can be done, for example, by reacting hexamethyldisilazane with the silicate tackifying resin. Such reactions can be catalyzed, for example, by trifluoroacetic acid. Alternatively, trimethylchlorosilane or trimethylsilylacetamide can be reacted with the silicate tackifying resin, in which case no catalyst is required.

[0109] MQD silicone tackifying resins can be, for example, R'SiO, as taught in U.S. Pat. No. 2,736,721 (Dexter). 1 / 2 Units ("M" units), SiO 4 / 2 unit ("Q" unit), and R'2SiO 2 / 2 MQD silicone tackifying resins are terpolymers having R'SiO units. 2 / 2 A portion of the methyl R' groups of the "D" units are replaced with vinyl (CH2=CH-) groups ("D Vi " units).

[0110] MQT silicate tackifying resins are, for example, R'3SiO as taught in U.S. Pat. No. 5,110,890 (Butler) and JP-A-2-36234. 1 / 2 Units, SiO 4 / 2 Units, and R'SiO 3 / 2 It is a terpolymer having units ("T" units).

[0111] Suitable silicate tackifying resins are commercially available from sources such as Dow Corning (Midland, MI), General Electric Silicones (Waterford, NY) and Rhodia Silicones (Rock Hill, SC). Particularly useful examples of MQ silicate tackifying resins include those available under the trade names SR-545 and SR-1000, both of which are commercially available from GE Silicones (Waterford, NY). Such resins are generally supplied in organic solvents and may be used as received in the formulation of the adhesives of the present disclosure. A blend of two or more silicate resins may be included in the adhesive composition.

[0112] The tackifier is typically added to the composition at least 10 wt%, in some embodiments at least 30 wt%, in some embodiments at least 40 wt%, and in some embodiments at least 50 wt%, based on the total weight of the adhesive composition. The tackifier is typically present in the composition at 70 wt% or less, 65 wt% or less, and in some embodiments at 60 wt% or less, based on the total weight of the adhesive composition. In typical adhesive compositions herein, the tackifier is present in the composition at about 60 wt% or less and 40 wt% or more. Without being bound by theory, a concentration of tackifier greater than about 60 wt% means that in certain conditions, the tackifier takes the continuous phase of the composition in favor of the silicone-containing polymer. Adhesive compositions having a tackifier that forms a continuous phase tend to exhibit at least one of poor tack, poor adhesion, poor shear holding strength, and poor damage-free removal.

[0113] Inorganic fillers and other additives By combining the silicone-containing polymer and silicate tackifying resin with inorganic particles or other fillers, either pressure-sensitive or heat-activated adhesives can be formulated. Inorganic particles included in the adhesive composition tend to improve the performance of the resulting adhesive. More specifically, inorganic particles tend to increase the adhesion of pressure-sensitive adhesives and increase the rubbery plateau modulus. Surprisingly, the addition of inorganic particles reduces the adhesive residue remaining on the substrate, reduces the peel force required to remove the adhesive, reduces the potential for damage to the adherend, and reduces adhesion to certain release liners when the adhesive is stretched or peeled for removal after being adhered to the substrate, without substantially sacrificing shear strength and attachment ability.

[0114] The inorganic particles can be uniformly or non-uniformly dispersed throughout the pressure-sensitive adhesive composition. The inorganic particles can be any suitable metal, metal alloy, metal oxide, ceramic material, or mixtures thereof. The inorganic particles are often selected from, but are not limited to, alumina, titania, zirconia, silica, and the like.

[0115] In many embodiments, the inorganic particles are fumed silica particles. Suitable fumed silicas are commercially available, for example, from Evonik Industries (Essen, Germany) under the trade name AEROSIL (e.g., AEROSIL R972, R974, R976, R300, R380, R130, R150, R200, R202, R805, and R812), or from Cabot (Alpharetta, GA) under the trade name CABOSIL (e.g., CABOSIL TS-720, TS-610, TS-530, and TS-500). The fumed silica can have any suitable surface area. For example, the surface area can be from 1 to 500 m 2 / g range, 10~400m 2 / g range or 100-400m 2The fumed silica may be in the range of 1 / gram. The fumed silica may have any suitable particle size. In some applications, the fumed silica has an average primary particle size of less than 30 microns, less than 15 microns, less than 10 microns, less than 5 microns, and less than 1 micron. Although nanoscale fumed silica can be used in certain implementations, the use of fumed silica with an average primary particle size of less than 200 nanometers may result in damage to the substrate. Although hydrophobic or hydrophilic fumed silica can be used, hydrophobic fumed silica is often used because the particles tend to disperse better in the organic solvents typically contained in various compositions.

[0116] In other embodiments, the inorganic particles are aerogels, such as silica aerogel particles (e.g., crushed aerogels or aerogel powders). Silica aerogel particles often have pores in the nanometer range (e.g., less than 100 nanometers or less than 50 nanometers) and have a diameter of at least 500 nm. 2 The silica aerogel particles have a surface area equal to 1000 nm / gram. Exemplary aerogel silica particles can have an average particle size of less than 20 microns or less than 10 microns. Although the size of silica aerogel particles is larger than the wavelength of light, the particles are often translucent and can be used to form adhesive layers that are relatively transparent, even if not considered optically transparent. Exemplary silica aerogel particles in translucent and opaque grades are commercially available from Cabot (Billerica, MA) under the trade name NANOGEL.

[0117] Inorganic particles can be surface-modified to facilitate dispersion in silicone polymer or adhesive composition, but inorganic particles are often not surface-modified. Inorganic particles can be agglomerated or non-agglomerated, aggregated or non-aggregated. Inorganic particles can have any desired particle size or particle shape. When an optically transparent adhesive article is desired, inorganic particles are often selected to have an average particle size of less than 1000 nanometers. For example, the average particle size is often less than 500 nanometers, less than 200 nanometers, less than 100 nanometers, or less than 50 nanometers. Larger inorganic particles can be used to prepare adhesive articles that do not need to be optically transparent. For example, inorganic particles can have an average particle size of up to 5 microns, up to 10 microns, up to 20 microns, up to 50 microns, or up to 100 microns.

[0118] Typically, the inorganic particles are added at a concentration of about 0.1% to about 20% by weight, based on the total weight of the adhesive composition, or any amount within that range. In currently preferred implementations, the inorganic particles are added at a concentration of about 2% to about 15% by weight, about 3% to about 13% by weight, and about 4% to about 10% by weight, based on the total weight of the adhesive composition, and any amount within those specified ranges. Filler loadings of less than 20% by weight, particularly filler loadings within the currently preferred ranges, can promote the adhesive composition to exhibit at least one of damage-free removal, repositionability, and high shear strength, even in wet or humid environments (as shown at least by the results of the examples below). For example, a filler loading of about 4% to about 7% by weight can be useful in high humidity and on relatively smooth surfaces such as bathroom or kitchen tiles. As another example, a filler loading of about 5% to about 13% by weight can be particularly suitable for textured or irregular surfaces (e.g., drywall). Such compositions can also exhibit reduced adhesion to certain silicone release liners, allowing the user to quickly prepare an article for object attachment or other adhesive-related operations.

[0119] The adhesive composition may further include other additives to provide desired properties. For example, dyes and pigments can be added as colorants, conductive and / or thermally conductive compounds can be added to make the adhesive conductive and / or thermally conductive or antistatic, antioxidants and antimicrobial agents can be added, and UV stabilizers and absorbers, such as hindered amine light stabilizers (HALS), can be added to stabilize the adhesive against UV degradation and block certain UV wavelengths from passing through the article. Other additives include, but are not limited to, adhesion promoters, additional fillers (e.g., carbon fibers, carbon black, glass beads, glass and ceramic bubbles, glass fibers, mineral fibers, clay particles, organic fibers such as nylon, metal particles, or unexpanded polymeric microspheres), adhesion enhancers, blowing agents, hydrocarbon plasticizers, and flame retardants.

[0120] Method for producing adhesive composition In certain solvent-based processes, the silicate tackifying resin can be incorporated before, during, or after the polyamine and polyisocyanate are introduced into the reaction mixture. The reaction of the polyamine and polyisocyanate is carried out in a solvent or mixture of solvents. The solvents are preferably non-reactive with the polyamine and polyisocyanate. The starting materials and the final product preferably remain completely miscible in the solvent during and after the polymerization is completed. These reactions can be carried out at room temperature or below the boiling point of the reaction solvent. The reaction is preferably carried out at ambient temperatures of up to 50°C.

[0121] In the substantially solvent-free process, the polyamine, polyisocyanate and silicate tackifying resin are mixed in a reactor and the reactants are reacted to form a silicone-polyurea block copolymer, which is combined with the tackifying resin to form the pressure sensitive adhesive composition.

[0122] One useful method involving the combination of solvent-based and solventless processes includes preparing the silicone polyurea block copolymer using a solventless process, and then mixing the silicone polyurea block copolymer with a silicate tackifying resin solution in a solvent.Typically, the silicone polyurea block copolymer-based pressure-sensitive adhesive composition is prepared by the above-mentioned combination method to produce a blend of the silicone polyurea block copolymer and the tackifying resin.

[0123] The adhesive composition may be solvent-free or may contain a solvent. Suitable solvents include, but are not limited to, toluene, tetrahydrofuran, dichloromethane, aliphatic hydrocarbons (e.g., alkanes such as hexane), or mixtures thereof.

[0124] ADHESIVE ARTICLE AND METHOD FOR MANUFACTURING ADHESIVE ARTICLE An adhesive article is provided that includes a substrate and an adhesive layer adjacent to at least one surface of the substrate. Other adhesive articles of the present disclosure may not include a backing or substrate. Backing-free adhesive structures are described, for example, in US Patent Application Publication No. 2016 / 0068722 (Schmitz Stapela et al.). Some embodiments of the adhesive layer include at least one of: (1) a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of about 0.1% to about 70% by weight, and a fumed silica in an amount of about 0.1% to about 20% by weight; (2) a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 0.1% to about 70% by weight, and a fumed silica in an amount of about 0.1% to about 20% by weight; and (3) an addition cure silicone, a silicate tackifying resin in an amount of about 0.1% to about 70% by weight, and a fumed silica in an amount of about 0.1% to about 20% by weight. The substrate may include a single layer of material or may be a combination of two or more materials.

[0125] The substrate can have any useful form, including, but not limited to, a film, a sheet, a membrane, a filter, a non-woven or woven fiber, a hollow or solid bead, a bottle, a plate, a tube, a rod, a pipe, or a wafer. The substrate can be porous or non-porous, rigid or flexible, transparent or opaque, colorless or colored, and reflective or non-reflective. The substrate can have a flat or relatively flat surface, or can have texture, such as wells, indentations, channels, bumps, etc. The substrate can have a single layer or multiple layers of material. Suitable substrate materials include, for example, polymeric materials, glass, ceramics, sapphire, metals, metal oxides, hydrated metal oxides, or combinations thereof.

[0126] Suitable polymeric substrate materials include, but are not limited to, polyolefins (e.g., polyethylenes such as biaxially oriented polyethylene or high density polyethylene and polypropylenes such as biaxially oriented polypropylene), polystyrenes, polyacrylates, polymethacrylates, polyacrylonitriles, polyvinyl acetates, polyvinyl alcohols, polyvinyl chlorides, polyoxymethylenes, polyesters such as polyethylene terephthalate (PET), polytetrafluoroethylenes, ethylene vinyl acetate copolymers, polycarbonates, polyamides, rayons, polyimides, polyurethanes, phenolics, polyamines, amino-epoxy resins, polyesters, silicones, cellulosic polymers, polysaccharides, nylons, neoprene rubbers, or combinations thereof. Some polymeric materials are foams, woven fibers, nonwoven fibers, or films.

[0127] Suitable glass and ceramic substrate materials can include, for example, silicone, aluminum, lead, boron, phosphorous, zirconium, magnesium, calcium, arsenic, gallium, titanium, copper, or combinations thereof. Glasses typically include various types of silicate-containing materials.

[0128] Some substrates are release liners. The adhesive layer is applied to a release liner and then transferred to another substrate, such as a backing film or foam substrate. Suitable release liners typically contain polymers such as polyester or polyolefin, or coated paper. Some adhesive articles are transfer tapes that include an adhesive layer located between two release liners. Exemplary release liners include, but are not limited to, polyethylene terephthalate coated with fluorosilicone, such as those disclosed in U.S. Pat. No. 5,082,706 (Tangney) and commercially available from Loparex, Inc., Bedford Park, IL. The liner can have a microstructure on its surface, which is imparted to the adhesive to form a microstructure on the surface of the adhesive layer. The liner can be removed to obtain an adhesive layer with a microstructured surface.

[0129] In some embodiments, the adhesive article is a single-sided adhesive tape with an adhesive layer on a single major surface of a substrate, such as a foam or film. In other embodiments, the adhesive article is a double-sided adhesive tape with an adhesive layer on two major surfaces of a substrate, such as a foam or film. The two adhesive layers of the double-sided adhesive tape can be the same or different. For example, one adhesive can be a pressure-sensitive adhesive and the other can be a heat-activated adhesive, where at least one of the adhesives is based on a polydiorganosiloxane polyoxamide or silicone polyurea block copolymer. Each exposed adhesive layer can be applied to another substrate.

[0130] The adhesive article may contain additional layers, such as primers, barrier coatings, metallic and / or reflective layers, tie layers, and combinations thereof, which may be located between the substrate and the adhesive layer, adjacent to the substrate on the opposite side of the adhesive layer, or adjacent to the adhesive layer on the opposite side of the substrate.

[0131] Some adhesive articles of the present disclosure have excellent shear strength. Some embodiments of the present disclosure have a shear strength of more than 1800 minutes when measured by ASTM D3654-82, modified according to the following static shear test method. Some embodiments of the present disclosure have a shear strength of more than 10,000 minutes when measured by modified ASTM D3654-82. Some embodiments of the present disclosure have a shear strength of more than 50,000 minutes when measured by modified ASTM D3654-82.

[0132] Some adhesives that can be used in the adhesive articles of the present disclosure have a glass transition temperature, as determined by dynamic mechanical analysis of the tan δ peak value, of about −125° C. to 15° C. Some adhesives that can be used in the adhesive articles of the present disclosure have a storage modulus at 25° C. of about 400,000 Pa or less, or 300,000 or less, as measured by dynamic mechanical analysis.

[0133] In some embodiments, the thickness of the adhesive on at least one of the first or second major surfaces of the multi-layer carrier is from about 1 μm to about 1 mm.

[0134] Some adhesive articles of the present disclosure have an elongation to break of greater than 50% in at least one direction. Some adhesive articles of the present disclosure have an elongation to break of from about 50% to about 1200% in at least one direction.

[0135] Some adhesive articles of the present disclosure have a tensile break strength high enough that the adhesive article does not tear before being removed from the substrate at an angle of 35° or less.

[0136] Some adhesive articles of the present disclosure have a lower peel force (e.g., a force of about 25 oz / in to about 50 oz / in) to make the adhesive article easier to remove. Some adhesive articles of the present disclosure can have a higher peel force (e.g., a force of about 50 oz / in to about 100 oz / in) to allow the user to handle the adhesive article without accidental separation. Some embodiments of the present disclosure have a peel force of about 20 oz / in to about 90 oz / in. Some embodiments of the present disclosure have a peel force of about 30 oz / in to about 70 oz / in.

[0137] Some adhesive articles of the present disclosure have a tensile break strength high enough that the adhesive article does not tear before being removed from the substrate at an angle of 35° or greater.

[0138] Methods for making adhesive articles typically include providing a substrate and applying an adhesive composition to at least one surface of the substrate. The adhesive composition can be applied to the substrate by a wide range of processes, such as, for example, solution coating, solution spraying, hot melt coating, extrusion, coextrusion, lamination, and pattern coating. Adhesive compositions are often applied to substrates with a viscosity of 0.02 grams / 154.8 cm. 2 ~2.4g / 154.8cm 2 is applied as an adhesive layer to the surface of the substrate at a coating weight of 1000g.

[0139] The adhesive articles of the present disclosure may be subjected to post-processing steps such as curing, crosslinking, die cutting, heating to cause expansion of the article, such as foam-in-place.

[0140] Hard Good Some embodiments of the adhesive articles described herein further include a hardgood or attachment device. Exemplary hardgoods or attachment devices include, for example, hooks, knobs, clips, and loops. In some embodiments, the hardgood resembles a nail. In some embodiments, the hardgood has a single outward protrusion to serve as a hanging surface. In some embodiments, the hardgood has multiple outward protrusions to serve as hanging surfaces. In some embodiments, the hardgood is shaped to hold one or more items inside, such as, but not limited to, a box or caddy. In some embodiments, the hardgood is a shelf, ledge, or platform. In some embodiments, the hardgood is a bar, which may be straight or curved, or may be substantially a ring, and which may be attached parallel or perpendicular to the substrate surface. In some embodiments, the hardgood uses multiple methods to attach or hang an article. Any of the following attachment devices may be used with the adhesive articles of the present disclosure: Application No. 77486US002 (assigned to the present assignee), U.S. Pat. Nos. 5,409,189 (Luhmann), 5,989,708 (Kreckel), 8,708,305 (McGreevy), 5,507,464 (Hamerski et al.), 5,967,474 (doCanto et al.), 6,082,686 (Schumann), 6,131,864 (Schumann), 6,811,126 (Johansson et al.), D665,653, and 7,028,958 (Pitzen et al.), all of which are incorporated herein by reference in their entirety. A hardgood can be any object that is attached to a substrate.

[0141] In some embodiments, the hardgoods are attached to the substrate at one or more locations, with one or more of the attachment locations including removable adhesive portions featuring one or more adhesive compositions described herein. In some embodiments, the hardgoods are attached using a combination of removable adhesive portions and conventional mechanical fasteners, such as, but not limited to, nails, screws, bolts, and rivets.

[0142] In some embodiments, the hardgood is made from a thermoplastic polymer. In some embodiments, the hardgood is made from a thermosetting polymer. In some embodiments, the hardgood is made from a polyolefin material. In some embodiments, the hardgood is made from a polycarbonate material. In some embodiments, the hardgood is made from a high impact polystyrene. In some embodiments, the hardgood is made from an acrylonitrile-butadiene-styrene (ABS) terpolymer. In some embodiments, the hardgood is made from two or more polymeric materials. In some embodiments, the hardgood is made from a metal. In some embodiments, the hardgood is made from stainless steel. In some embodiments, the metal is painted, polished, stained, brushed, or coated to modify its appearance. In some embodiments, the hardgood is made from a ceramic. In some embodiments, the hardgood is made from a polished ceramic. In some embodiments, the hardgood is made from a non-polished ceramic. In some embodiments, the hardgood is made from a natural material such as wood, bamboo, particle board, cloth, canvas, or a material derived from a biological source. In some embodiments, the natural-based materials may be painted, polished, stained, or coated to change their appearance. In some embodiments, the hardgoods are made using two or more materials from the list above. In some embodiments, the hardgoods are made from two pieces that are reversibly or irreversibly attached, joined, or welded.

[0143] In some embodiments, the hardgood comprises two parts, a first part serves as a mounting surface for attaching the compliant and removable layers to a substrate, and a second part serves as a hanging member that can be used to suspend or attach an object to the substrate. The two parts may be reversibly attached using mechanical fasteners, hook and loop materials, or an additional adhesive layer.

[0144] The hardgoods can be manufactured using any method known in the art. In some embodiments, the removable adhesive may be attached to the hardgoods using a lamination process. In some embodiments, the removable adhesive (and substrate, if present) may be attached to the hardgoods using a multiple lamination process.

[0145] In some embodiments, the removable adhesive may be applied to the hardgoods using two or more injection molding processes using one or more molds.

[0146] In some embodiments, the removable adhesive may be applied manually by the end user.

[0147] In some embodiments, the adhesive article can further include a separable connector. Some exemplary separable connectors are described, for example, in U.S. Patent Nos. 6,572,945, 7,781,056, 6,403,206, and 6,972,141, all of which are incorporated by reference herein in their entirety.

[0148] Methods of using the adhesive articles described herein The articles of the present disclosure can be used in a variety of ways. In some embodiments, the adhesive article is applied, attached, or pressed onto the adherend. In this way, the adhesive article comes into contact with the adherend. If a release liner is present, the release liner is removed before the adhesive article is applied, attached, or pressed onto the adherend. In some embodiments, at least a portion of the adherend is wiped with alcohol before the adhesive article is applied, attached, or pressed onto the adherend.

[0149] The adhesive article may be used in wet or humid environments such as those found in bathrooms. For example, the adhesive article may be adhered to toilets (e.g., toilet tanks), bathtubs, sinks, and walls. The adhesive article may be used in showers, locker rooms, steam rooms, pools, hot tubs, and kitchens (e.g., kitchen sinks, dishwashers, and backsplash areas, refrigerators and coolers). The adhesive article may also be used in outdoor applications and low temperature applications such as refrigerators. Useful outdoor applications include bonding articles such as signs to outdoor surfaces such as windows, doors, and vehicles.

[0150] The adhesive article (i.e., adhesive tape or in a single article) can be provided in any useful form, such as, for example, a tape, strip, sheet (e.g., perforated sheet), label, roll, web, disk, and kit (e.g., an object for attachment and an adhesive tape used to attach the object). Similarly, multiple adhesive articles can be provided in any suitable form, including, for example, a tape, strip, sheet (e.g., perforated sheet), label, roll, web, disk, kit, stack, tablet, and combinations thereof, in any suitable packaging, including, for example, a dispenser, bag, box, and carton.

[0151] To remove the adhesive article from the substrate, at least a portion of the adhesive article is peeled or stretch-released from the substrate. In some embodiments, the stretch angle is 35° or less. In embodiments where a tab is present, a user can grasp the tab and use it to peel or remove the adhesive article from the substrate.

[0152] The adhesive articles may be used to attach a variety of articles and objects to surfaces such as painted drywall, plaster, concrete, glass, ceramic, fiberglass, metal or plastic, etc. Attachable items include, but are not limited to, wall hangers, organizers, holders, baskets, containers, non-slip mats, decorations (e.g., holiday decorations), calendars, posters, dispensers, wire clips, body side moldings on vehicles, handles, road signs, vehicle markings, transportation markings, and signage applications such as reflective sheeting.

[0153] The foregoing describes the present disclosure in terms of embodiments that the inventors anticipated and have found useful description, but also indicates that even imaginable, as yet unforeseen modifications of the present disclosure may represent equivalents of the present invention. EXAMPLES

[0154] These examples are merely for illustrative purposes only and are not meant to limit the scope of the appended claims. All parts, percentages, ratios, etc. in the examples and elsewhere herein are by weight unless otherwise indicated.

[0155] Test Method Test Method 90° Angle Peel Adhesion Strength Test Peel adhesion strength and removability were evaluated by the following method: Test strips (multilayer composite tapes as described below) were applied to the substrates with a 15 pound roller pressure. The bonded samples were aged at 72°F (22°C) and 50% RH (CTH) conditions for at least 1 hour dwell time before testing. Unless otherwise noted, the strips were peeled from the panels using an INSTRON Universal Testing Machine with a crosshead speed of 12 in / min (30.5 cm / min) (some samples were run at 90 in / min (228.6 cm / min)). The peel force was measured and the panel was observed to see if any visible adhesive residue was left or if any damage had occurred. The peel data in the table represents the average of three tests.

[0156] Peel Damage Codes - To test the effect of peel adhesion on drywall, the following system of qualitative coding was assigned to different levels of damage. [Table 1]

[0157] Shear Strength Test Shear strength was determined by ASTM D3654-82 method. A test square (multilayer composite tape as described below) was applied to the adherend and a metallized PET film measuring 0.5 or 0.75 in. wide by approximately 4 in. long (1.27 or 1.91 cm wide by 10.16 cm long) was attached to the opposing (non-peelable) adhesive. The metallized PET was folded over and stapled. A 15 pound roller was then used to press down the sample with two passes. The sample was mounted in a vertical position and allowed to sit at CTH conditions (unless otherwise noted) for 60 minutes, after which a load of 750 or 1000 grams was applied to the adhesive. The sample was hung until failure or until at least 25,000 minutes had elapsed (note that 10,000 minutes is the ASTM time limit).

[0158] Package Weight Claim Test Multi-layer composite tape samples were prepared with DUAL LOCK strip backing as described below. Test samples were cut into 0.75 in x 0.75 in (1.91 cm x 1.91 cm) squares. Each sample was used in pairs for each test. For each pair, one was applied to painted drywall by sticking the silicone adhesive side to the drywall with the DUAL LOCK backing facing out. The second piece was applied silicone adhesive side to a 1 in x 2 in (2.54 cm x 5.08 cm) aluminum panel, also with the DUAL LOCK backing facing out. A 15.4 lb roller was used to apply consistent pressure (two passes) to the piece applied to the drywall at a speed of 12 in / min to achieve proper wet out. The two pieces (one on the drywall, the other on the aluminum panel) were joined by clamping the DUAL LOCK sides together. The samples were mounted in a vertical position and allowed to rest on the test substrate for 60 minutes at the specified conditions (either CTH or 72°F / 75% RH). After the 1 hour rest period had elapsed, a 1000 gram weight was applied to the sample by hanging a weight on an aluminum panel. Damage was indicated if the adhesive square was observed to have completely fallen off the test substrate (the adhesive was no longer adhering to the test substrate surface). Package weight demand data in the tables is provided as Weight Retention (days). Data is an average of three tests.

[0159] Some package weight tests were conducted at FEN 72°F / 75% RH conditions using a medium size Command™ utility hook (strip size: 5 / 8″×2″, available from 3M Company).

[0160] Several package weight tests were also conducted in a shower spray chamber at 95% RH with a continuous H2O spray at water temperatures of 105°F to 120°F (41°C to 49°C). A medium size Command™ utility hook (strip size: 5 / 8" x 2", available from 3M Company) was used in this test. The specimens were adhered to White Glazed Ceramic Wall Tile (Interceramic, Carrollton, TX) and the load on the specimen was 3 lbs.

[0161] Liner peel test The samples were tested under CTH conditions.

[0162] Easy side: A 2.54 cm wide, approximately 20 cm long sample of adhesive transfer tape on liner was cut using a test strip razor cutter. At least four transfer adhesive tapes prepared as described below were placed on top of each other, with the adhesive side on each strip in contact with the liner side of the next strip. A stack of at least two strips was applied lengthwise onto the platen surface of a peel adhesion tester (IMASS SP-2100 tester, available from IMASS, Inc., Accord, Mass.) using 3M Double Coated Paper Tape 410M (available from 3M Company, St. Paul, Minn., USA). The top strip was peeled from the bottom liner at a 180 degree angle, for example, at 60 in / min (152.4 cm / min). The average force required to peel the three strips from their underlying counterparts was recorded as the easy-side liner peel.

[0163] Tight side: A 2.54 cm wide, approximately 20 cm long sample of the adhesive transfer tape on the liner was cut using a specimen razor cutter. The cut sample was applied lengthwise onto the platen surface of a peel adhesion tester (IMASS SP-2100 tester, available from IMASS, Inc., Accord, Mass.) using 3M Double Coated Paper Tape 410M (available from 3M Company, St. Paul, Minn., USA). The release liner was peeled from the adhesive at a 180 degree angle, for example, at 12 in / min (30.5 cm / min). The average force required to peel the three liners from the adhesive was recorded as the tight side liner peel.

[0164] Rheological measurements Rheological properties were performed in torsion mode using a dynamic mechanical analyzer Discovery HR-3 (TA Instruments, New Castle, Del.) equipped with 8 mm parallel plate grips. Samples were prepared by folding the PSA four times to give an adhesive thickness of approximately 1 mm. Samples were cut into 8 mm diameter disks using a punch cutter made specifically for the purpose.

[0165] During testing, an initial static axial force of 50-300gr was applied in compression mode to ensure that the adhesive was adequately stressed during testing. A 50% strain adjustment was always kept in active mode to ensure that no axial deformation occurred in the specimens during the experiment. Temperature was controlled using a nitrogen purged force convection oven. Sub-ambient temperatures were achieved using a special liquid nitrogen Dewar supplied by TA Instruments. The specimens were loaded at an initial test temperature of 25°C and the temperature was reduced in 3°C increments during the experiment down to a final temperature of -65°C. At each temperature step, the specimens were subjected to a torsional oscillation of 5% strain at a frequency of 1 rad / s. The results were plotted as a function of temperature. Shear storage modulus (G'), loss modulus (G") and tan δ (defined as the value of the ratio of loss modulus / storage modulus (G" / G')) were reported at a particular temperature such as 25°C.

[0166] Test substrate Drywall panels (obtained from Materials Company, Metzger Building, St. Paul, MN) were painted with Behr PREMIUM PLUS ULTRA® Primer and Paint 2 in 1 Flat Egyptian Nile (FEN) (obtained from Behr Process Corporation, Santa Ana, CA) or Sherwin-Williams DURATION® Interior Acrylic Latex Ben Bone White Paint SWBB (obtained from Sherwin-Williams Company, Cleveland, OH). The third paint used for peel adhesion testing was Clark+Kensington Semi-Gloss Acrylic Latex, Paint and Primer Designer White (CS) from Ace Hardware.

[0167] Painting procedure: A first coat of paint was applied to the panel using a paint roller, followed by air drying at ambient conditions for 24 hours. A second coat of paint was applied and allowed to dry at ambient conditions for 24 hours. The panels were placed in a forced air oven set at 50° C. for 7 days. The panels were then stored at ambient conditions until use.

[0168] Glass and painted drywall panels measuring 2 in x 2 in (5.1 cm x 5.1 cm) were used for shear strength testing. Glass and painted drywall panels measuring 6 in x 12 in (15.2 cm x 30.5 cm) were used for peel adhesion and package weight demand testing at 72°F / 75% RH.

[0169] Preparation of adhesive transfer tape The pressure sensitive adhesive composition was knife coated onto a paper liner web having a fluoroalkyl silicone release surface. The paper liner web speed was 2.75 meters / min. After coating, the web was passed through an 11 meter long oven with three temperature zones (total residence time 4 minutes). The temperature in zone 1 (2.75 meters) was 57°C, the temperature in zone 2 (2.75 meters) was 80°C, and the temperature in zone 3 (approximately 5.5 meters) was 93°C. The caliper of the dried adhesive was approximately 2.5-3.0 mils thick. The adhesive transfer adhesive tape was then stored at ambient conditions.

[0170] The addition cure examples were coated using a manual hand spread coater. The same caliper was applied to obtain a dry adhesive thickness of 2.5-3.0 mils. After coating, the adhesive was cured in a convection oven at 120°C for 3 minutes.

[0171] Preparation of multilayer composite tapes The transfer adhesive was then laminated to the film-foam-film composite and die cut to the desired size and shape. Specifically, the test adhesive composition was adhered to a first side of a composite film-foam-film structure similar to that found in the COMMAND strip product (31 mil 6 lb foam with 1.8 mil polyethylene film on both sides of the foam). This side of the film-foam-film structure was primed with 3M Adhesion Promoter 4298UV (3M Company, St. Paul, MN) prior to adhesive lamination. The second side of the composite foam had a second non-peeling adhesive adhered along the entire width and length of the test sample. 3M DUAL LOCK strip backing or 2 mil PET film was adhered to the second side for peel adhesion and package weight demand testing, or a metallized PET film was adhered to the second side for shear testing. Samples of the adhesive coated film-foam-film composite were die cut into 1 in wide by 6 in long strips (2.54 cm x 15.24 cm) for peel testing from painted drywall, or 0.5 in x 0.5 in (1.27 cm x 1.27 cm) for shear testing, or 0.75 in x 0.75 in (1.91 cm x 1.91 cm) for package weight demand testing.

[0172] Preparation of surface modified fumed silica To a glass bottle, 250 g of Cab-O-Sperse 2017A (available as a silica dispersion in water at approximately 17% solids from Cabot Corp., Alpharetta, GA, USA) was added. With magnetic stirring, 250 g of isopropanol was slowly added. To this mixture, 10.29 g of hexadecyltrimethoxysilane (available as Silane 25013VP from Wacker Chemical Corp., Adrian, MI, USA) and 0.45 g of methyltrimethoxysilane (available as Silane M1-Trimethoxy from Wacker Chemical Corp., Adrian, MI, USA) were added. The bottle was tightly sealed with a cap and the combined mixture was heated and stirred in a water bath at 80° C. for 24 hours. After cooling to room temperature, the contents were transferred to a flask and rinsed with toluene. The water and isopropanol were removed on a rotary evaporator and the volume was periodically exchanged with additional toluene until the resulting dispersion was 16.5% solids in toluene.

[0173] Examples E1 to E12 and Comparative Examples CE1 to CE4 Silicone Polyurea Block Copolymer Pressure Sensitive Adhesive Formulations Fumed silica (AEROSIL® 812 S available from Evonik Corporation, Parsippany, NJ) was added to an empty 32 ounce jar and diluted with toluene and MQ tackifying resin (SR545, supplied as a 30% by weight solids solution in toluene, available from Momentive Performance Materials, Watertown, NY). The resulting mixture was placed on a paint shaker set on high for 15 minutes to create a thick iridescent dispersion. An elastomer solution of silicone polyurea block copolymer (in 65 / 35 toluene / isopropyl alcohol) was then added to the jar, sealed, and the jar was placed on a roller for 18 hours, mixing set at approximately 25 rpm. The silicone polyurea block copolymer (SPU) was the same as the silicone polyurea block copolymer used to prepare the pressure sensitive adhesive composition of Example 28 of U.S. Pat. No. 6,569,521. Adhesive transfer tapes and multi-layer composite tapes were prepared as described above. The pressure sensitive adhesive formulations and percent solids used in the coatings are provided in Table 1. The rheological properties of the pressure sensitive adhesives are provided in Table 2.

[0174] [Table 2]

[0175] [Table 3]

[0176] [Table 4]

[0177] [Table 5]

[0178] [Table 6]

[0179] [Table 7]

[0180] [Table 8]

[0181] [Table 9]

[0182] [Table 10]

[0183] [Table 11]

[0184] Examples E13 to E22 The pressure sensitive adhesive formulations of Examples E13-E22 were prepared according to the general procedure described for Examples E1-E12. The adhesive transfer tape and multi-layer composite tape were prepared as described above. The pressure sensitive adhesive formulations and percent solids used for coating are provided in Table 11. The rheological properties of the pressure sensitive adhesives are provided in Table 12.

[0185] [Table 12]

[0186] [Table 13]

[0187] [Table 14]

[0188] [Table 15]

[0189] [Table 16]

[0190] [Table 17]

[0191] Examples E23 to E26 The pressure sensitive adhesive formulations of Examples E23-E26 were prepared according to the general procedure described in Examples E1-E12, except that CABOSIL TS-382 (available from Cabot Corporation, Boston, Mass.) was the fumed silica used in Examples E24 and E26 instead of AEROSIL R 812 S. Adhesive transfer tapes and multi-layer composite tapes were prepared as described above. The pressure sensitive adhesive formulations and percent solids used for coating are provided in Table 17. The rheological properties of the pressure sensitive adhesives are provided in Table 18.

[0192] [Table 18]

[0193] [Table 19]

[0194] [Table 20]

[0195] [Table 21]

[0196] Examples E27 to E30 The pressure sensitive adhesive formulations of Examples E27-E30 were prepared following the general procedure described in Examples E1-E12, substituting AEROSIL R 812S, a silica using surface modified silica nanoparticles prepared as described above. Adhesive transfer tapes and multi-layer composite tapes were prepared as described above. The pressure sensitive adhesive formulations and percent solids used for coating are provided in Table 21. The rheological properties of the pressure sensitive adhesives are provided in Table 22.

[0197] [Table 22]

[0198] [Table 23]

[0199] [Table 24]

[0200] [Table 25]

[0201] Examples E31 to E46 The pressure sensitive adhesive formulations of Examples E31-E46 were prepared following the general procedure described for Examples E1-E12. The adhesive transfer tape and multi-layer composite tape were prepared as described above. The pressure sensitive adhesive formulations and percent solids used for coating are provided in Table 25. The rheological properties of the pressure sensitive adhesives are provided in Table 26.

[0202] [Table 26]

[0203] [Table 27]

[0204] [Table 28]

[0205] [Table 29]

[0206] Examples E47 to E55 and Comparative Examples CE6 to CE8 Silicone polydisiloxane polyoxamide block copolymer pressure sensitive adhesive formulations Fumed silica (AEROSIL® 812 S available from Evonik Corporation, Parsippany, NJ) was added to an empty 32 ounce jar and diluted with toluene and MQ tackifying resin (SR545 available from Momentive Performance Materials, Watertown, NY). The resulting mixture was placed on a paint shaker set on high for 15 minutes to create a thick iridescent dispersion. An elastomer solution of polydisiloxane polyoxamide block copolymer (in 77 / 23 ethyl acetate / isopropyl alcohol) was then added to the jar, sealed, and the jar was placed on a roller for 18 hours, mixing at approximately 25 rpm. The polydisiloxane polyoxamide block copolymer (PDMS I) used was the same as that used in the pressure sensitive adhesive composition of Example 12 of U.S. Pat. No. 8,765,881. Example 12 shows an amine with an equivalent weight of 10,174 g / mol, or a molecular weight of about 20,000 g / mol. Adhesive transfer tapes and multi-layer composite tapes were prepared as described above. The pressure sensitive adhesive formulations and percent solids used for coating are provided in Table 29.

[0207] [Table 30]

[0208] [Table 31]

[0209] [Table 32]

[0210] [Table 33]

[0211] Examples E56 to E61 and Comparative Examples CE9 to CE11 Addition-Cure Silicone Pressure-Sensitive Adhesive Formulations In the first step, silica powder was individually added to toluene to make a silica stock solution. After the silica was added to the toluene, the mixture was placed on a medium strength shaker and shaken for 10 minutes. The sample was then placed on a mixing roller and left to sit until it was time to use it in the next step. In the next step, the appropriate amount of 0.2 weight fraction PDMS (PDMS II) solution (Wacker 948 available from Wacker Chemie AG, Germany, supplied as a 30 wt% solids solution in toluene) was weighed based on the formulation and added to an 8 oz jar. Then, MQ tackifier resin (SR545 available from Momentive Performance Materials, Watertown, NY, supplied as a 30 wt% solids solution in toluene) was added to the PDMS solution in the appropriate amount. The silica stock solution was then added to the PDMS / MQ resin mixture. Finally, a crosslinker (SYL-OFF 7678 crosslinker, available from Dow Chemical Company, Midland, MI) was added to the solution in the appropriate amount (based on a hydride to vinyl ratio of 6) and the solution was placed on a mixing roller and left on the roller overnight to achieve proper mixing. Just prior to coating the adhesive, 40 ppm of platinum catalyst (platinum-divinyltetramethyldisiloxane complex, available from Gelest, Morrisville, PA) was added to the solution. The solution was placed on the roller for mixing for 10 minutes prior to coating. Adhesive transfer tapes and multi-layer composite tapes were prepared as described above. Pressure sensitive adhesive formulations are provided in Table 33.

[0212] [Table 34]

[0213] [Table 35]

[0214] [Table 36]

[0215] Embodiment 1. (a) a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and about 0.1% to about 20% by weight of fumed silica; (b) a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and a fumed silica in an amount of about 0.1% to about 20% by weight, or (c) an addition cure silicone, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and a fumed silica in an amount of about 0.1% to about 20% by weight; 1. An adhesive composition comprising: 2. The adhesive composition of embodiment 1, wherein the adhesive composition comprises a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and about 0.1% to about 20% by weight of fumed silica. 3. The adhesive composition of embodiment 1, wherein the adhesive composition comprises a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and a fumed silica in an amount of about 0.1% to about 20% by weight. 4. The adhesive composition of embodiment 1, wherein the adhesive composition comprises an addition cure silicone, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and a fumed silica in an amount of about 0.1% to about 20% by weight. 5. The adhesive composition according to any one of embodiments 1 to 4, which is a pressure-sensitive adhesive. 6. The adhesive composition according to any one of embodiments 1 to 4, which is a heat-activated adhesive. 7. The adhesive composition of any one of embodiments 1 to 6, wherein the silicate tackifying resin is an MQ silicate tackifying resin. 8. The adhesive composition of any one of the preceding embodiments, wherein the tackifier is present in an amount of about 20 weight percent to about 60 weight percent, based on the weight of the adhesive composition. 9. The adhesive composition of embodiment 8, wherein the tackifier is present in an amount of about 40 weight percent to about 60 weight percent, based on the weight of the adhesive composition. 10. The adhesive composition of any one of the preceding embodiments, wherein the fumed silica is present in an amount of about 1 weight percent to about 15 weight percent, based on the weight of the adhesive composition. 11. The adhesive composition of embodiment 10, wherein the fumed silica is present in an amount of about 2 weight percent to about 10 weight percent, based on the weight of the adhesive composition. 12. An article comprising a substrate and an adhesive layer adjacent to at least one surface of the substrate, the adhesive layer comprising: (a) a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and about 0.1% to about 20% by weight of fumed silica; (b) a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and a fumed silica in an amount of about 0.1% to about 20% by weight, or (c) an addition cure silicone, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and a fumed silica in an amount of about 0.1% to about 20% by weight; An article comprising at least one of the following: 13. The article of embodiment 12, wherein the adhesive layer comprises a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and about 0.1% to about 20% by weight of fumed silica. 14. The article of embodiment 12, wherein the adhesive layer comprises a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and fumed silica in an amount of about 0.1% to about 20% by weight. 15. The article of embodiment 12, wherein the adhesive composition comprises an addition cure silicone, a silicate tackifying resin in an amount of about 10% to about 70% by weight, and a fumed silica in an amount of about 0.1% to about 20% by weight. 16. The article of any one of embodiments 12-15, wherein the adhesive layer is a heat-activated adhesive. 17. The article of any one of embodiments 12-15, wherein the adhesive layer is a pressure-sensitive adhesive. 18. The article of any one of embodiments 12-15, wherein the silicate tackifying resin comprises an MQ silicate tackifying resin. 19. The article of any one of the preceding embodiments, wherein the tackifier is present in an amount from about 30 weight percent to about 60 weight percent, based on the weight of the adhesive composition. 20. The article of embodiment 18, wherein the tackifier is present in an amount from about 40 weight percent to about 60 weight percent, based on the weight of the adhesive composition. 21. The article of any one of the preceding embodiments, wherein the fumed silica is present in an amount of about 2 weight percent to about 10 weight percent, based on the weight of the adhesive composition. 22. The article of embodiment 21, wherein the fumed silica is present in an amount from about 3 weight percent to about 9 weight percent, based on the weight of the adhesive composition. 23. The article of any one of claims 11 to 22, having a peel adhesion of from about 0.5 oz / in to about 120 oz / in and a shear retention of at least about 1500 minutes. 24. The article of any one of claims 11 to 23, having a static shear of at least about 30,000 minutes. 25. The article of embodiment 24, having a static shear of at least about 50,000 minutes. 26. The article of any one of embodiments 11-23, further comprising a release liner in contact with the surface of the adhesive layer. 27. The article of embodiment 24, wherein the peel adhesion of the adhesive layer to the release liner is 100 oz / in or less. 28. The article of embodiment 24, wherein the peel adhesion of the adhesive layer to the release liner is 50 oz / in or less. 29. The article of any one of embodiments 24-28, wherein the fumed silica has an average particle size of at least about 200 nanometers and no greater than about 20 microns. 30. The article of embodiment 29, wherein the fumed silica has an average particle size of at least about 1 micron and no greater than about 15 microns. 31. A method for preparing an adhesive article, comprising: Providing an adhesive composition according to any one of embodiments 1 to 11; and applying the adhesive composition to a surface of a substrate.

[0216] All recitations of value ranges by endpoints are intended to include all numbers subsumed within that range (ie, the range 1 to 10 includes, for example, 1, 1.5, 3.33, and 10).

[0217] Terms such as first, second, third, etc. in the detailed description and embodiments are used to distinguish between similar elements and do not necessarily describe an order or chronology. It is to be understood that the terms so used are interchangeable under appropriate circumstances and that the embodiments of the invention described herein can function in orders other than those described or illustrated herein.

[0218] Moreover, terms such as top, bottom, upper, lower, and the like, in the detailed description and embodiments are used for descriptive purposes and do not necessarily describe relative positions, with it being understood that the terms so used are interchangeable under appropriate circumstances, and that the embodiments of the invention described herein can function in orientations other than those described or illustrated herein.

[0219] All references mentioned herein are incorporated by reference in their entirety.

[0220] It will be appreciated that connector systems may have many different characteristics that are particularly suitable for a particular application or for connecting together particular types of objects, and thus, although any such connector system may be used in accordance with the present invention, a connector system selected based on characteristics that are particularly suitable for a particular application or for connecting together particular types of objects may be advantageously chosen.

Claims

1. a first substrate having a first major surface and a second major surface; a first adhesive layer on the first major surface of the first substrate; a second adhesive layer on the second major surface of the first substrate; and a second substrate adjacent to the second adhesive layer; wherein the first adhesive layer comprises: (a) a polydiorganosiloxane polyoxamide copolymer, a silicate tackifying resin in an amount of from about 30% to about 60% by weight, and from about 0.1% to about 15% by weight of fumed silica, or (b) a silicone polyurea block copolymer, a silicate tackifying resin in an amount of about 30% to about 60% by weight, and a fumed silica in an amount of about 0.1% to about 15% by weight; wherein said weight is based on the total weight of said first adhesive layer; the first adhesive layer has a glass transition temperature of about -125°C to 15°C; The article comprises: 90° peel adhesion of about 0.5 oz / in to about 120 oz / in on drywall at 72° F. (22° C.) and 50% RH after 1 hour dwell time at a crosshead speed of 12 in / min (30.5 cm / min); Shear retention of at least 1 day on drywall at 72°F (22°C) and 75% RH, as determined by Package Weight Demand Testing; and 6.6 lbs / in on drywall at 72°F (22°C) 50% RH 2 (464 g / cm 2 ) having a static shear of greater than 1800 minutes as measured by a shear strength test at a load of 1000 psi.

2. The article of claim 1 , wherein the fumed silica has an average particle size of at least about 1 micron and no greater than about 15 microns.

3. The article of claim 1 , wherein the silicate tackifying resin comprises an MQ silicate tackifying resin.

4. The article of claim 1, wherein the silicate tackifying resin is present in an amount of about 40% to about 60% by weight, based on the total weight of the first adhesive layer.

5. The article of claim 1 , wherein the fumed silica is present in an amount of about 2% to about 15% by weight, based on the total weight of the first adhesive layer.

6. The article of claim 5, wherein the fumed silica is present in an amount of about 3% to about 9% by weight, based on the total weight of the first adhesive layer.

7. The article of claim 1 further comprising a release liner in contact with a surface of the first adhesive layer.

Citation Information

Patent Citations

  • Curable silicone composition and its manufacture

    JP1991128937A

  • Laminated body containing additive hardenable silicone adhesive composition

    JP1993124150A

  • Adhesive polydiorganosiloxane polyurea segmented copolymer and method of making same

    JP1999505560A

  • Addition-curable silicone rubber composition and pressure-sensitive adhesive rubber sheet

    JP2006225420A

  • Removable film-forming GEL compositions featuring adhesion promoters

    WO2018071278A1